Method for manufacturing a polyester resin composition

CN116075543BActive Publication Date: 2026-10-30TOYOBO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202180062031.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-11
Filing Date
2021-09-01
Publication Date
2026-10-30
Estimated Expiration
2041-09-01

AI Technical Summary

Benefits of technology

[0051]通过本发明的制造方法制造的聚酯树脂组合物,即使也使用由铝化合物和磷化合物构成的聚合催化剂,也能抑制低的催化剂成本,并且通过使用降低聚酯树脂中所含的来源于催化剂的异物的基体聚酯树脂,能够降低制作聚酯树脂组合物中耗费的成本,提升聚酯树脂组合物的品质。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004117287950000101
    Figure BDA0004117287950000101
  • Figure BDA0004117287950000171
    Figure BDA0004117287950000171
  • Figure BDA0004117287950000331
    Figure BDA0004117287950000331
Patent Text Reader

Abstract

Provided is a method for producing a polyester resin composition, which can reduce catalyst cost and has few foreign substances even when a polymerization catalyst composed of an aluminum compound and a phosphorus compound is used. A method for producing a polyester resin composition, characterized by having a step of mixing a base polyester resin (A) containing an aluminum compound and a phosphorus compound and satisfying the following (1) to (3), and a master batch (B) containing an antiblocking agent.(1) The content of aluminum elements in the base polyester resin (A) is 9 to 19 mass ppm(2) The content of phosphorus elements in the base polyester resin (A) is 13 to 31 mass ppm(3) The molar ratio of phosphorus elements to aluminum elements in the base polyester resin (A) is 1.32 or more and 1.80 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for manufacturing a polyester resin composition. Background Technology

[0002] Polyester resins, represented by polyethylene terephthalate (PET), polybutylene terephthalate (PBT), and polyethylene naphthalate (PEN), have excellent mechanical and chemical properties. Based on the characteristics of each polyester resin, they are widely used in various fields such as textile and industrial fiber, packaging or industrial films and sheets, bottles and engineering plastics.

[0003] Polyester resins that are representative of polyester resins and whose main components are units derived from aromatic dicarboxylic acids and alkylene glycols, such as polyethylene terephthalate (PET), are manufactured industrially by esterification or transesterification of terephthalic acid or dimethyl terephthalate with ethylene glycol to produce bis(2-hydroxyethyl) terephthalate, which is then polycondensed under high temperature and vacuum using a catalyst.

[0004] Antimony compounds or germanium compounds have long been widely used as catalysts for polyester polymerization, particularly in the polymerization of polyester resins like these. Antimony trioxide, an example of an antimony compound, is inexpensive and possesses excellent catalytic activity. However, when used as a main component at a level sufficient to achieve a practical polymerization rate, metallic antimony precipitates during polymerization, resulting in black spots and foreign matter on the polyester resin, contributing to surface defects in the film. Furthermore, when used as a raw material for hollow molded products, it is difficult to obtain hollow molded products with excellent transparency. For these reasons, polyester resins completely free of antimony compounds or with antimony compounds as the main catalyst component are desired.

[0005] Germanium compounds have been put into practical use as catalysts with excellent catalytic activity, other than antimony compounds, and without causing the aforementioned problems to polyester resins. However, germanium compounds have drawbacks, such as being very expensive and the tendency for them to distill out of the reaction system during polymerization, leading to changes in the catalyst concentration and making polymerization control difficult. Therefore, their use as the main component of a catalyst is problematic.

[0006] Polymerization catalysts that can replace antimony or germanium compounds have been studied, and titanium compounds, represented by tetraalkoxytitanate, have been proposed. However, polyester resins made using titanium compounds are prone to thermal degradation during melt molding, and there is also the problem of significant coloration of the polyester resin.

[0007] For these reasons, there is a desire for polymerization catalysts that use metals other than antimony, germanium, and titanium as the main metal component of the catalyst, and that produce polyester resins with excellent catalytic activity, excellent color and thermal stability, and excellent transparency of the molded product.

[0008] For example, Patent Documents 1 and 2 disclose catalysts composed of aluminum and phosphorus compounds as novel polymerization catalysts. However, Patent Documents 1 and 2 suffer from the problem of increased catalyst content and high cost of phosphorus compounds, resulting in both increased catalyst cost and decreased polymerization activity.

[0009] In addition, when using polyester resin to manufacture polyester film, it is usually necessary to form surface protrusions on the surface of the resulting polyester film by using an anti-blocking agent to improve the film's slip properties, operational stability, abrasion resistance, rollability, and other operational characteristics.

[0010] On the other hand, Patent Document 3 discloses a polyester composition for membranes containing a polyester resin without inorganic particles and a polyester composition for masterbatch containing inorganic particles, manufactured using a catalyst composed of aluminum and phosphorus compounds. In this technology, due to the large amount of catalyst added, especially phosphorus compounds, and the high cost of the phosphorus compounds used, the cost of the catalyst required for polymerization increases.

[0011] Existing technical documents

[0012] Patent documents

[0013] [Patent Document 1] International Publication No. 2007 / 032325

[0014] [Patent Document 2] Japanese Patent Application Publication No. 2006-169432

[0015] [Patent Document 3] International Publication No. 2013 / 146524 Summary of the Invention

[0016] The problem the invention aims to solve

[0017] The present invention was made to solve the problems of the prior art. Its purpose is to improve the polymerization activity and reduce the catalyst cost in the method of manufacturing polyester resin composition using a base polyester resin, even if the base polyester resin used is a polymerization catalyst composed of aluminum and phosphorus compounds, and to produce a polyester resin with fewer foreign matter.

[0018] Technical means to solve the problem

[0019] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that by reducing the amount of aluminum in the matrix polyester resin and making the molar ratio of phosphorus to aluminum within an appropriate range, the purpose of the present invention was achieved.

[0020] When using polymerization catalysts such as antimony compounds and germanium compounds in polyester polymerization, the polymerization activity is usually proportional to the amount of catalyst added. However, for polymerization catalysts composed of aluminum and phosphorus compounds, the polymerization activity is not simply related to the amount of catalyst added because the complexation reaction between aluminum and phosphorus compounds affects the polymerization activity.

[0021] Here, the inventors analyzed the factors affecting the activity of a polymerization catalyst composed of aluminum and phosphorus compounds. The results showed that by reducing the amount of aluminum in the matrix polyester resin and maintaining an appropriate molar ratio of phosphorus to aluminum, polymerization activity could be improved while suppressing the increase in the amount of aluminum-based foreign matter, thus completing this invention.

[0022] That is, the present invention consists of the following components.

[0023] [1] A method for manufacturing a polyester resin composition, characterized in that it comprises a step of mixing a matrix polyester resin (A) containing an aluminum compound and a phosphorus compound and satisfying the following (1) to (3) and a masterbatch (B) containing an anti-blocking agent.

[0024] (1) The aluminum content in the matrix polyester resin (A) is 9-19 ppm by mass.

[0025] (2) The phosphorus content in the matrix polyester resin (A) is 13-31 ppm by mass.

[0026] (3) The molar ratio of phosphorus to aluminum in the matrix polyester resin (A) is between 1.32 and 1.80.

[0027] [2] The method for manufacturing the polyester resin composition described in [1], wherein the masterbatch (B) contains insoluble particles that are insoluble particles in the matrix polyester resin (A), the volume average particle size of the insoluble particles is 0.5 to 3.0 μm, and the content of the insoluble particles is 0.5 to 20% by mass.

[0028] [3] A method for manufacturing the polyester resin composition described in [1] or [2], wherein a masterbatch (C) containing an electrostatic adhesion promoter is further mixed.

[0029] [4] The method for manufacturing the polyester resin composition described in [3], wherein the masterbatch (C) is a polyester resin containing magnesium compound, alkali metal compound and phosphorus compound, wherein the masterbatch (C) contains 400 to 2700 ppm by mass of magnesium, 40 to 270 ppm by mass of alkali metal and 200 to 1700 ppm by mass of phosphorus.

[0030] [5] A method for manufacturing the polyester resin composition described in [1] or [2], wherein, instead of the masterbatch (B), a masterbatch (D) containing an anti-blocking agent and an electrostatic adhesion promoter is mixed with the base polyester resin (A).

[0031] [6] The method for manufacturing the polyester resin composition described in [5], wherein the masterbatch (D) contains insoluble particles that are insoluble in the matrix polyester resin (A), the volume average particle size of the insoluble particles is 0.5 to 3.0 μm, and the content of the insoluble particles is 0.5 to 20% by mass. Further, the masterbatch (D) contains 400 to 2700 ppm by mass of magnesium, 40 to 270 ppm by mass of alkali metals, and 200 to 1700 ppm by mass of phosphorus.

[0032] [7] The method for manufacturing the polyester resin composition described in [4] or [6], wherein the alkali metal contained in the masterbatch (C) or the masterbatch (D) is potassium.

[0033] [8] A method for manufacturing a polyester resin composition according to any one of [4], [6] or [7], wherein the phosphorus compound contained in the masterbatch (C) or the masterbatch (D) is a trialkyl phosphate, wherein at least one of the alkyl groups of the trialkyl phosphate is an alkyl group having 2 to 4 carbon atoms.

[0034] [9] The method for manufacturing the polyester resin composition described in [8], wherein the phosphorus compound contained in the masterbatch (C) or the masterbatch (D) is triethyl phosphate.

[0035]

[10] A method for manufacturing the polyester resin composition of any one of [3] to [9], wherein the melt resistivity of the masterbatch (C) or the masterbatch (D) is 0.005×10⁸ to 0.05×10⁸ Ω·cm.

[0036]

[11] The method for manufacturing the polyester resin composition according to any one of [3] to

[10] , wherein the masterbatch (C) or the masterbatch (D) is a polyester with dicarboxylic acid and diol as constituent components, and when the amount of magnesium relative to the dicarboxylic acid is set to m (mol%), the amount of alkali metal is set to k (mol%), and the amount of phosphorus is set to p (mol%), the following (4) is satisfied.

[0037] (4) 2≤(m+k / 2) / p≤3.5

[0038]

[12] A method for manufacturing the polyester resin composition of any one of [1] to

[11] , wherein the phosphorus compound contained in the matrix polyester resin (A) has a phosphorus element and a phenol structure in the same molecule.

[0039]

[13] The method for manufacturing the polyester resin composition of any one of [1] to

[12] , wherein the content of aluminum element in the matrix polyester resin (A) equivalent to aluminum-based foreign matter is less than 3000 ppm by mass.

[0040]

[14] A method for manufacturing the polyester resin composition described in any one of [1] to

[13] , wherein the intrinsic viscosity (IV) of the matrix polyester resin (A) is 0.56 dl / g or higher.

[0041]

[15] The method for manufacturing the polyester resin composition of any one of [1] to

[14] , wherein the method for manufacturing the matrix polyester resin (A) comprises a first step of synthesizing a polyester or an oligomer thereof as an intermediate condensation polymer, and a second step of further condensing the intermediate; after the first step and before the second step, a solution A1 containing dissolved aluminum compound and a solution B1 containing dissolved phosphorus compound are added to the intermediate, wherein the amounts of solution A1 and solution B1 added satisfy the following (5) to (7).

[0042] (5) The amount of aluminum added relative to the generated matrix polyester resin (A) is 9 to 19 ppm by mass.

[0043] (6) The amount of phosphorus added relative to the generated matrix polyester resin (A) is 18 to 38 ppm by mass.

[0044] (7) The molar ratio of the amount of phosphorus added in (6) to the amount of aluminum added in (5) is more than 1.50 and less than 2.30.

[0045]

[16] The method for manufacturing the polyester resin composition described in

[15] , wherein the matrix polyester resin (A) is manufactured by a batch polymerization method.

[0046]

[17] The method for manufacturing the polyester resin composition described in

[15] , wherein the matrix polyester resin (A) is manufactured by continuous polymerization, and the solution A1 and the solution B1 are added to the final esterification reactor or the delivery line between the final esterification reactor and the initial polymerization reactor.

[0047]

[18] A method for manufacturing the polyester resin composition of any one of

[15] to

[17] , wherein the solution A1 is a diol solution and the maximum absorption wavelength of the solution A1 is 562.0 to 572.0 nm.

[0048]

[19] The method for manufacturing the polyester resin composition described in

[18] , wherein the solution B1 is a diol solution and the maximum absorption wavelength of the solution B1 is 458.0 to 465.0 nm.

[0049]

[20] The method for manufacturing the polyester resin composition of any one of

[15] to

[19] , wherein the solution A1 and the solution B1 are diol solutions, and the maximum absorption wavelength of the mixture of the diol solution A1 and the diol solution B1 is 559.5 to 560.8 nm.

[0050] Invention Effects

[0051] The polyester resin composition manufactured by the manufacturing method of the present invention can suppress low catalyst costs even when using a polymerization catalyst composed of aluminum compounds and phosphorus compounds. Furthermore, by using a matrix polyester resin that reduces foreign matter from the catalyst contained in the polyester resin, the cost of manufacturing the polyester resin composition can be reduced, and the quality of the polyester resin composition can be improved.

[0052] Furthermore, by setting the acidity and alkalinity of the aluminum compound solution, phosphorus compound solution, and mixture thereof added as catalysts to a preferred range (setting the maximum absorption wavelength of the solution or mixture to a preferred range), the amount of aluminum-based foreign matter in the matrix polyester resin can be further suppressed.

[0053] Furthermore, since the polyester resin composition obtained by the manufacturing method of the present invention can be obtained at low cost and with high quality, the production cost of polyester film obtained by forming the polyester resin composition into a film can also be reduced, and the quality of the polyester film can be improved. Moreover, due to the excellent operational stability, abrasion resistance, and optical properties of this polyester film, it can be used in a wide range of applications such as packaging films and industrial films. Attached Figure Description

[0054]

【 Figure 1 The graph showing the relationship between the residual molar ratio of phosphorus to aluminum, the amount of aluminum-based foreign matter, and the polymerization time, obtained from the results of the examples and comparative examples.

[0055]

【 Figure 2 The graph shows the relationship between the maximum absorption wavelength of the mixture of phosphorus-containing glycol solution and aluminum-containing glycol solution and the amount of aluminum foreign matter and polymerization time, obtained from the results of the examples and comparative examples.

[0056]

【 Figure 3The graph shows the relationship between the maximum absorption wavelength and the back pressure rise coefficient of the mixture of aluminum-containing glycol solution and phosphorus-containing glycol solution, obtained from the results of the examples and comparative examples. Detailed Implementation

[0057] The present invention will now be described in detail.

[0058] The method for manufacturing the polyester resin composition of the present invention includes a step of mixing a base polyester resin (A) and a masterbatch (B) containing an anti-blocking agent. It should be noted that the base polyester resin (A) will be referred to as "polyester resin (A)" below, and the masterbatch (B) containing the anti-blocking agent may also be referred to as "masterbatch (B) containing anti-blocking agent" or simply "masterbatch (B)".

[0059] [Polyester Resin (A)]

[0060] Polyester resin (A) contains aluminum compounds and phosphorus compounds. In addition, polyester resin (A) satisfies the following (1) to (3).

[0061] (1) The aluminum content in polyester resin (A) is 9-19 ppm by mass.

[0062] (2) The phosphorus content in polyester resin (A) is 13-31 ppm by mass.

[0063] (3) The molar ratio of phosphorus to aluminum in polyester resin (A) is between 1.32 and 1.80.

[0064] It should be noted that in this instruction manual, ppm refers to 10 -4 The meaning of % (percentage of mass).

[0065] The polyester resin (A) comprises a polyester resin consisting of at least one selected from polycarboxylic acids and their ester-forming derivatives and at least one selected from polyols and their ester-forming derivatives.

[0066] As for the polyester resin (A), the main polycarboxylic acid component is preferably a dicarboxylic acid. Furthermore, the main polyol component is preferably a diol.

[0067] Polyester resin (A) whose main polycarboxylic acid component is dicarboxylic acid refers to a polyester resin containing at least 70 mol% dicarboxylic acid relative to the total polycarboxylic acid components, more preferably at least 80 mol% and even more preferably at least 90 mol%. It should be noted that when two or more dicarboxylic acids are used, their total content is preferably within the above range.

[0068] Examples of dicarboxylic acids include saturated aliphatic dicarboxylic acids or their ester-forming derivatives, such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, dodecanedicarboxylic acid, tetradecanedicarboxylic acid, hexadecanedicarboxylic acid, 1,3-cyclobutanedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,5-norbornenedicarboxylic acid, and dimer acids; and fumaric acid, maleic acid, and icariin. Unsaturated aliphatic dicarboxylic acids or their ester-forming derivatives, such as acids; aromatic dicarboxylic acids or their ester-forming derivatives, such as phthalic acid, isophthalic acid, terephthalic acid, 5-(alkali metal)sulfonyl isophthalic acid, biphenyl dicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-biphenyl dicarboxylic acid, 4,4'-diphenyl sulfone dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, papoic acid, anthracene dicarboxylic acid, etc.

[0069] More preferably, the main polycarboxylic acid component is terephthalic acid or its ester-forming derivative, or naphthalic acid or its ester-forming derivative. Examples of naphthalic acid or its ester-forming derivative include 1,3-naphthalic acid, 1,4-naphthalic acid, 1,5-naphthalic acid, 2,6-naphthalic acid, 2,7-naphthalic acid, or their ester-forming derivatives.

[0070] The polyester resin whose main polycarboxylic acid component is terephthalic acid or its ester-forming derivatives or naphthalic acid or its ester-forming derivatives refers to a polyester resin that preferably contains 70 mol% or more of terephthalic acid or its ester-forming derivatives and naphthalic acid or its ester-forming derivatives relative to the total amount of all polycarboxylic acid components, more preferably contains 80 mol% or more of polyester resin, and even more preferably contains 90 mol% or more of polyester resin.

[0071] Particularly preferred are terephthalic acid, 2,6-naphthalenedicarboxylic acid, or their ester-forming derivatives. Other dicarboxylic acids may also be used as constituents if desired.

[0072] As polycarboxylic acids other than these dicarboxylic acids, if in small quantities, polycarboxylic acids with three or more nucleotides and hydroxycarboxylic acids may be used together, preferably polycarboxylic acids with three to four nucleotides. Examples of polycarboxylic acids include ethanetricarboxylic acid, propanetricarboxylic acid, butanetetracarboxylic acid, pyromellitic acid, trimellitic acid, 3,4,3',4'-biphenyltetracarboxylic acid, and their ester-forming derivatives. The polycarboxylic acid with three or more nucleotides is preferably 20 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less, relative to the total polycarboxylic acid composition. It should be noted that when two or more polycarboxylic acids with three or more nucleotides are used, their total amount is preferably within the above range.

[0073] Examples of hydroxycarboxylic acids include lactic acid, citric acid, malic acid, tartaric acid, glycolic acid, 3-hydroxybutyric acid, p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, 4-hydroxycyclohexanecarboxylic acid, or their ester-forming derivatives. The hydroxycarboxylic acid content is preferably 20 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less, relative to the total polycarboxylic acid content. It should be noted that when two or more hydroxycarboxylic acids are used, their total content is preferably within the above range.

[0074] Examples of ester-forming derivatives of polycarboxylic acids or hydroxycarboxylic acids include their alkyl esters, acyl chlorides, acid anhydrides, etc.

[0075] As for polyester resin (A), diol is preferred as the main polyol component.

[0076] Polyester resin (A) whose main polyol component is diol refers to a polyester resin that, relative to the total polyol component, preferably contains 70 mol% or more of diol, more preferably 80 mol% or more, and even more preferably 90 mol% or more. It should be noted that when using two or more diols, their total content is preferably within the above range.

[0077] Examples of diols include ethylene glycol, 1,2-propanediol, 1,3-propanediol, diethylene glycol, triethylene glycol, 1,2-butanediol, 1,3-butanediol, 2,3-butanediol, 1,4-butanediol, 1,5-pentanediol, neopentanediol, 1,6-hexanediol, 1,2-cyclohexanediol, 1,3-cyclohexanediol, 1,4-cyclohexanediol, 1,2-cyclohexanediethanol, 1,3-cyclohexanediethanol, 1,4-cyclohexyldiethanol, 1,4-cyclohexyldiethanol, 1,10-decanediol, and 1,12-decanediol. Alkylene glycols, such as dialkyldiols; aliphatic glycols, such as polyethylene glycol, polypropylene glycol, and polybutanediol; aromatic glycols, such as hydroquinone, 4,4'-dihydroxybisphenol, 1,4-bis(β-hydroxyethoxy)benzene, 1,4-bis(β-hydroxyethoxyphenyl)sulfone, bis(p-hydroxyphenyl) ether, bis(p-hydroxyphenyl)sulfone, bis(p-hydroxyphenyl)methane, 1,2-bis(p-hydroxyphenyl)ethane, bisphenol A, bisphenol C, 2,5-naphthalenediol, and glycols to which ethylene oxide has been added.

[0078] Among these diols, alkylene glycols are preferred, and ethylene glycol, 1,3-propanediol, 1,4-butanediol, or 1,4-cyclohexanediol are more preferred. Furthermore, the molecular chain of the alkylene glycol may contain substituents or alicyclic structures, and two or more types may be used simultaneously.

[0079] As for polyols other than these diols, if in small quantities, polyols with 3 or more nucleotides may be used in combination, preferably polyols with 3 to 4 nucleotides. Examples of polyols with 3 or more nucleotides include trimethylolmethane, trimethylolethane, trimethylolpropane, pentaerythritol, glycerol, and hexanetriol.

[0080] Relative to the total polyol composition, the polyols with three or more components are preferably 20 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less. It should be noted that when using two or more polyols with three or more components, their total amount is preferably within the above range.

[0081] Furthermore, the use of cyclic esters is also permitted. Examples of cyclic esters include ε-caprolactone, β-propiolactone, β-methyl-β-propiolactone, δ-valerolactone, glycolide, and lactide. Additionally, ester-forming derivatives of polyols include esters of polyols with lower aliphatic carboxylic acids such as acetic acid.

[0082] Relative to the sum of all polycarboxylic acid components and all polyol components, the cyclic esters are preferably 20 mol% or less, more preferably 10 mol% or less, and even more preferably 5 mol% or less. It should be noted that when two or more cyclic esters are used, their sum is preferably within the above range.

[0083] The polyester resin (A) is preferably a polymer composed of only one monomer selected from polyethylene terephthalate, butylene terephthalate, propylene terephthalate, 1,4-cyclohexanedimethyl terephthalate, polyethylene naphthalate, butylene naphthalate, or propylene naphthalate, or a copolymer composed of two or more of the above monomers. More preferably, the polyester resin (A) is a copolymer composed of at least one of the above monomers other than polyethylene terephthalate or polyethylene terephthalate, and particularly preferably polyethylene terephthalate. The copolymer composed of at least one of the above monomers other than polyethylene terephthalate preferably contains 70 mol% or more of the component derived from polyethylene terephthalate monomer, more preferably 80 mol% or more, and even more preferably 90 mol% or more.

[0084] <Polymerization Catalyst>

[0085] Polyester resin (A) contains catalyst amounts derived from aluminum compounds and phosphorus compounds. That is, polyester resin (A) is manufactured using a polymerization catalyst composed of aluminum and phosphorus compounds.

[0086] <Aluminum Compounds>

[0087] There are no restrictions on the aluminum compounds constituting the above-mentioned polymerization catalyst, as long as they are soluble in solvents; known aluminum compounds can be used without limitation. Examples of aluminum compounds include, for instance, carboxylates such as aluminum formate, aluminum acetate, basic aluminum acetate, aluminum propionate, aluminum oxalate, aluminum acrylate, aluminum laurate, aluminum stearate, aluminum benzoate, aluminum trichloroacetate, aluminum lactate, aluminum citrate, aluminum tartrate, and aluminum salicylate; inorganic acid salts such as aluminum chloride, aluminum hydroxide, aluminum hydroxychloride, aluminum nitrate, aluminum sulfate, aluminum carbonate, aluminum phosphate, and aluminum phosphonate; aluminum alkoxides such as aluminum methoxide, aluminum ethoxide, aluminum n-propoxide, aluminum isopropoxide, aluminum n-butoxide, and aluminum tert-butoxide; chelates such as aluminum acetylacetone, aluminum ethyl acetoacetate, and aluminum diisopropoxide of ethyl acetoacetate; organoaluminum compounds such as trimethylaluminum and triethylaluminum, as well as their partial hydrolysis products, reaction products of aluminum alkoxides or aluminum chelates with hydroxycarboxylic acids, alumina, ultrafine alumina, aluminum silicate, and complex oxides of aluminum with titanium, silicon, zirconium, alkali metals, or alkaline earth metals. Among these, preferably at least one is selected from carboxylates, inorganic acid salts, and chelates; more preferably at least one is selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, aluminum hydroxychloride, and aluminum acetylacetonate; even more preferably at least one is selected from aluminum acetate, basic aluminum acetate, aluminum chloride, aluminum hydroxide, aluminum hydroxychloride, and aluminum acetylacetonate; particularly preferably at least one is selected from aluminum acetate and basic aluminum acetate; and most preferably basic aluminum acetate.

[0088] The aluminum compound described above is preferably an aluminum compound soluble in solvents such as water or glycols. Solvents that can be used in this invention include water and alkylene glycols. Examples of alkylene glycols include ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, trimethylene glycol, di(trimethylene glycol), tetramethylene glycol, di(tetramethylene glycol), neopentyl glycol, etc. Preferably, it is selected from at least one of ethylene glycol, trimethylene glycol, and tetramethylene glycol, more preferably ethylene glycol. The effects of this invention can be significantly achieved by using a solution in which the aluminum compound is dissolved in water or ethylene glycol, and is therefore preferred.

[0089] The aluminum content in the polyester resin (A) needs to be 9 to 19 ppm by mass, preferably 10 to 19 ppm by mass, more preferably 10 to 17 ppm by mass, and even more preferably 12 to 17 ppm by mass. If the aluminum content is less than 9 ppm by mass, the polymerization activity may not be fully realized. On the other hand, if it is greater than 19 ppm by mass, the amount of aluminum-based foreign matter may increase.

[0090] <Phosphorus compounds>

[0091] There are no particular limitations on the phosphorus compounds constituting the polymerization catalysts described above. However, the use of phosphonic acid compounds or phosphonophosphonic acid compounds is preferred as they significantly enhance the catalyst activity. Among these, the use of phosphonic acid compounds is even more preferred because it provides a particularly significant enhancement to the catalyst activity.

[0092] Among the aforementioned phosphorus compounds, phosphorus compounds having both phosphorus and phenol structures within the same molecule are preferred. There is no particular limitation as long as the phosphorus compound has both phosphorus and phenol structures within the same molecule. If one or more compounds selected from the group consisting of phosphonic acid compounds and hypophosphonic acid compounds having both phosphorus and phenol structures within the same molecule are used, the enhancement effect on catalyst activity is significant, and therefore preferred. If one or more phosphonic acid compounds having both phosphorus and phenol structures within the same molecule are used, the enhancement effect on catalyst activity is very significant, and therefore even more preferred.

[0093] In addition, as a phosphorus compound containing both phosphorus and phenolic elements within the same molecule, an example is P(=O)R. 1 (OR 2 (OR) 3 ) or P(=O)R 1 R 4 (OR 2 Compounds represented by ) etc. R 1 R represents a hydrocarbon group with 1 to 50 carbon atoms containing a phenolic portion, a hydrocarbon group containing a hydroxyl or halogen group, an alkoxy or amino substituent, or a hydrocarbon group with 1 to 50 carbon atoms in the phenolic structure. 4R represents hydrogen, a hydrocarbon group with 1 to 50 carbon atoms, or a hydrocarbon group with 1 to 50 carbon atoms containing substituents such as hydroxyl, halogen, alkoxy, or amino groups. 2 R 3 Each of these groups independently represents hydrogen, a hydrocarbon group with 1 to 50 carbon atoms, or a hydrocarbon group with 1 to 50 carbon atoms containing substituents such as hydroxyl or alkoxy groups. The hydrocarbon group may also contain branched structures, alicyclic structures such as cyclohexyl, or aromatic ring structures such as phenyl or naphthyl. R 2 and R 4 The ends can be bonded together.

[0094] Examples of phosphorus compounds having both a phosphorus element and a phenolic structure within the same molecule include, for example, p-hydroxyphenylphosphonic acid, dimethyl p-hydroxyphenylphosphonate, diethyl p-hydroxyphenylphosphonate, diphenyl p-hydroxyphenylphosphonate, bis(p-hydroxyphenyl)phosphonic acid, methyl bis(p-hydroxyphenyl)phosphonate, phenyl bis(p-hydroxyphenyl)phosphonate, p-hydroxyphenylphosphonic acid, methyl p-hydroxyphenylphosphonate, phenyl p-hydroxyphenylphosphonate, and 3,5-di-tert-butyl-4-hydroxybenzylphosphonate dialkyl ester as shown in Formula 1. Among phosphorus compounds having both a phosphorus element and a phenolic structure within the same molecule, phosphorus compounds having a hindered phenolic structure are particularly preferred, especially 3,5-di-tert-butyl-4-hydroxybenzylphosphonate dialkyl ester as shown in Formula 1.

[0095]

Chemistry 1

[0096]

[0097] In (Formula 1), X 1 X 2 These represent hydrogen atoms and alkyl groups having 1 to 4 carbon atoms, respectively.

[0098] The above X 1 X 2 The alkyl group preferably has 1 to 4 carbon atoms, more preferably 1 to 2. In particular, the ethyl ester with 2 carbon atoms is preferred because it is readily available from commercially available Irganox 1222 (manufactured by BASF).

[0099] It should be noted that the phosphorus compound used in this invention is preferably the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in Formula 1 above. Alternatively, modified versions containing 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester may also be used. Details regarding the modified versions are described below.

[0100] The phosphorus content in the polyester resin (A) is 13–31 ppm by mass, preferably 15–29 ppm by mass. If the phosphorus content is less than 13 ppm by mass, the polymerization activity may decrease and the amount of aluminum-based foreign matter may increase. On the other hand, if it is greater than 31 ppm by mass, the polymerization activity may actually decrease, and the amount of phosphorus compound added will increase the catalyst cost, which is not preferred.

[0101] <Molar ratio of phosphorus to aluminum in polyester resin (A)>

[0102] In polyester resin (A), controlling the molar ratio of phosphorus to aluminum (hereinafter referred to as the "residual molar ratio of phosphorus to aluminum," to distinguish it from the "added molar ratio of phosphorus to aluminum" described later) is also important, and it needs to be 1.32 to 1.80, preferably 1.38 to 1.68. As mentioned above, the aluminum and phosphorus elements in polyester resin (A) are derived from aluminum and phosphorus compounds used as polymerization catalysts for polyester resin (A), respectively. By using these aluminum and phosphorus compounds in a specific ratio, a catalytically active complex is functionally formed in the polymerization system, thereby achieving sufficient polymerization activity. If the residual molar ratio of phosphorus to aluminum is less than 1.32, the thermal stability and thermal oxidation stability may decrease, and the amount of aluminum-based foreign matter may increase. On the other hand, if the residual molar ratio of phosphorus to aluminum is greater than 1.80, the amount of phosphorus compound added becomes excessive, increasing the catalyst cost.

[0103] In this invention, in addition to the aforementioned aluminum and phosphorus compounds, other polycondensation catalysts such as antimony compounds, germanium compounds, and titanium compounds are used within a range that does not cause problems in the properties, processability, color, and other aspects of the polyester resin products obtained by the manufacturing method of this invention.

[0104] The antimony content in the polyester resin composition is preferably less than 30 ppm by mass, the germanium content is preferably less than 10 ppm by mass, and the titanium content is preferably less than 3 ppm by mass. However, for the purposes of this invention, it is preferable to avoid using the other polycondensation catalysts mentioned above as much as possible.

[0105] The intrinsic viscosity (IV) of the polyester resin (A) is preferably 0.56 dl / g or higher, more preferably 0.56 to 0.65 dl / g, and even more preferably 0.58 to 0.64 dl / g. When the intrinsic viscosity of the polyester resin (A) is lower than the above range, the mechanical strength and impact resistance of the molded article may become insufficient. On the other hand, when the intrinsic viscosity of the polyester resin (A) is higher than the above range, it is not preferred due to reduced economic efficiency.

[0106] [Manufacturing method of polyester resin (A)]

[0107] As a method for manufacturing polyester resin (A), apart from using a polyester polymerization catalyst formed from aluminum compounds and phosphorus compounds as a catalyst, and adding a polymerization catalyst as described in (5) to (7) below, it can be carried out by a method with known procedures.

[0108] (5) The amount of aluminum added relative to the generated polyester resin (A) is 9 to 19 ppm by mass.

[0109] (6) The amount of phosphorus added relative to the generated polyester resin (A) is 18 to 38 ppm by mass.

[0110] (7) The molar ratio of the amount of phosphorus added in (6) to the amount of aluminum added in (5) (hereinafter referred to as the "molar ratio of phosphorus to aluminum") is 1.50 to 2.30 or less.

[0111] As a method for manufacturing polyester resin (A), a preferred method includes a first step of synthesizing a polyester or an oligomer thereof as an intermediate condensate (lower-order condensate) and a second step of further condensing the intermediate.

[0112] Furthermore, it is preferable to add a solution A1 containing dissolved aluminum compounds and a solution B1 containing dissolved phosphorus compounds to the intermediate after the first step and before the second step, as described in (5) to (7) above. Since the polycarboxylic acids and their ester-forming derivatives, the small amounts of hydroxycarboxylic acids and their ester-forming derivatives, and the small amounts of cyclic esters used in the manufacture of polyester resin (A) do not distill out of the reaction system during polymerization, almost 100% of the amount initially added as a catalyst remains in the polyester resin (A) manufactured by polymerization, the mass of "the generated polyester resin (A)" can be calculated based on their amounts.

[0113] The method for manufacturing polyester or its oligomers, which are used as low-order condensates (oligopolymers) in this invention, is not particularly limited.

[0114] The manufacturing method of polyester resin (A) can be carried out using methods with existing known processes, except that a polyester polymerization catalyst formed from aluminum and phosphorus compounds is used as the catalyst, and the content of aluminum and phosphorus elements in the polyester resin (A) is adjusted such that the molar ratio of phosphorus to aluminum is within a specific range. For example, when manufacturing polyethylene terephthalate, it can be carried out by a direct esterification method, in which terephthalic acid and ethylene glycol and other desired copolymers are directly reacted, water is distilled off for esterification, and polycondensation is performed under normal or reduced pressure; or by a transesterification method, in which dimethyl terephthalate and ethylene glycol and other desired copolymers are reacted, methanol is distilled off for transesterification, and polycondensation is performed under normal or reduced pressure. Further, solid-state polymerization can be performed to increase the limiting viscosity, as needed. The polymerization can be a batch polymerization method or a continuous polymerization method. It should be noted that the amount (mass) of the polyester resin (A) produced can be calculated based on the amount (mass) of the polycarboxylic acid contained in the dicarboxylic acid or the like used as raw materials.

[0115] In any of these methods, the esterification or transesterification reaction can be carried out in one stage or in multiple stages. In the melt polymerization reaction, the number and size of the reactors, as well as the manufacturing conditions of each process, are not limited and can be appropriately selected. It can be carried out in one stage or in multiple stages, preferably in 2 to 5 stages, more preferably in 3 to 4 stages, and even more preferably in 3 stages. The melt polymerization reaction is preferably carried out in a continuous reaction apparatus. A continuous reaction apparatus refers to a method in which the reaction vessels for the esterification or transesterification reaction and the melt polymerization reaction vessel are connected by piping, and raw materials are continuously added to each reaction vessel without leaving them idle, transported through piping to the melt polymerization reaction vessel, and resin is extracted from the melt polymerization reaction vessel. It should be noted that in this case, continuous does not necessarily mean that raw materials are added and extracted continuously at all times; it can also be a small, sequential, intermittent operation, such as adding and extracting raw materials in batches, for example, using approximately 1 / 10 of the volume of the reaction vessel. When performing esterification or transesterification reactions in multiple stages and manufacturing polyester resin (A) by continuous polymerization, it is preferable to add a solution A1 containing dissolved aluminum compounds and a solution B1 containing dissolved phosphorus compounds to the transport line between the final reaction tank (final esterification tank or final esterification reaction tank) and the initial polymerization tank.

[0116] Alternatively, polyester resin (A) produced by melt polycondensation can be further polymerized by solid-state polymerization. Solid-state polymerization can be carried out in a continuous process, just like melt polycondensation.

[0117] In a continuous polycondensation unit consisting of three or more reactors (a three-stage polymerization process with an initial stage, an intermediate stage, and a final stage), the first stage is designated as the initial stage, the final stage as the final stage, and the stage from the second stage to the stage preceding the final stage is designated as the intermediate stage. The reaction conditions for the polymerization reaction in the intermediate stage are preferably between the reaction conditions of the initial stage and the reaction conditions of the final stage. It is preferable to smoothly distribute the increase in intrinsic viscosity achieved in each of these polymerization reaction steps.

[0118] In this invention, the concentration of acid-terminated groups in the intermediate (lower-order condensate) prepared by the first step is preferably 400–1500 eq / ton, more preferably 500–1200 eq / ton. By setting the concentration of acid-terminated groups of the oligomer within the above range, the activity of the polymerization catalyst can be sufficiently initiated.

[0119] Furthermore, in this invention, the ratio (OH%) of the hydroxyl terminus to the total terminal group concentration of the aforementioned intermediate is preferably 45-70 mol%, more preferably 55-65 mol%. If the hydroxyl terminus ratio of the oligomer is less than 45 mol%, the polycondensation activity becomes unstable, and the amount of aluminum-based foreign matter may increase. On the other hand, if the hydroxyl terminus ratio of the oligomer is greater than 70 mol%, the polycondensation activity may decrease.

[0120] When aluminum and phosphorus compounds are used as catalysts, they are preferably added in the form of suspensions or solutions, more preferably in solutions dissolved in solvents such as water or glycols, even more preferably in solutions dissolved in water and / or glycols, and most preferably in solutions dissolved in ethylene glycol.

[0121] In this invention, preferably after the esterification reaction or transesterification reaction is completed, a solution A1 containing dissolved aluminum compound and a solution B1 containing dissolved phosphorus compound are added such that the content (residual amount) of aluminum and phosphorus elements in polyester resin (A) meets the range of (1) to (3) above.

[0122] By adding solutions A1 containing dissolved aluminum compounds and B1 containing dissolved phosphorus compounds to the polyester resin (A) such that the content (residual amount) of aluminum and phosphorus elements in the polyester resin (A) meets the ranges of (1) to (3) above, a complex with catalytic activity can be functionally formed in the polymerization system, thus exerting sufficient polymerization activity. In addition, the formation of aluminum-based foreign matter can also be suppressed.

[0123] It should be noted that, even when the polymerization of polyester resin (A) is carried out under reduced pressure, almost 100% of the aluminum atoms in the aluminum compound that function as a catalyst remain in the polyester resin (A) produced by polymerization. That is, since the amount of aluminum compound hardly changes before and after polycondensation, when the amount of aluminum added relative to the intermediate is 9 to 19 ppm by mass, the aluminum content in the polyester resin (A) is also 9 to 19 ppm by mass.

[0124] Furthermore, the phosphorus compound, which functions as a catalyst along with the aluminum compound, is discharged from the system during the polymerization of polyester resin (A) under reduced pressure, as part of the initial amount added to the catalyst system (approximately 10-40%). This removal ratio varies depending on the molar ratio of phosphorus to aluminum, the alkalinity or acidity of the added aluminum-containing glycol solution or phosphorus-containing glycol solution, and the method of adding the aluminum-containing or phosphorus-containing solution (added after liquefaction or added separately). Therefore, it is preferable to appropriately set the amount of phosphorus compound added so that the phosphorus content in the final product of polyester resin (A) satisfies the above-mentioned (2).

[0125] In this invention, it is preferable to simultaneously add a solution A1 containing dissolved aluminum compounds and a solution B1 containing dissolved phosphorus compounds. A more preferred embodiment is to pre-mix the solutions A1 and B1 at the ratio to be added to the intermediate to prepare a mixture, and then add the liquefied mixture to the intermediate. This method allows for a more stable application of the effects of the invention. Examples of pre-liquefaction include mixing the solutions in a tank or merging the pipelines containing the catalyst during transport.

[0126] It should be noted that when adding to the reaction vessel, it is preferable to increase the stirring speed of the reaction vessel. When adding to the piping between reaction vessels, it is preferable to use an in-line mixer or similar equipment to ensure that the added catalyst solution is mixed quickly and uniformly.

[0127] Adding solutions A1 (containing dissolved aluminum compounds) and B1 (containing dissolved phosphorus compounds) separately can lead to the formation of more foreign matter caused by aluminum compounds, a decrease in crystallization temperature upon heating, an increase in crystallization temperature upon cooling, and insufficient catalyst activity. Simultaneous addition of aluminum and phosphorus compounds allows for the rapid and efficient formation of a complex that enhances polymerization activity. In contrast, separate additions result in insufficient complex formation, and aluminum compounds that fail to form a complex with the phosphorus compound may precipitate as foreign matter.

[0128] Furthermore, the solutions A1 containing dissolved aluminum compounds and B1 containing dissolved phosphorus compounds are preferably added after the esterification or transesterification reaction is completed, and more preferably added to the intermediate after the first step and before the second step. If added before the esterification or transesterification reaction is completed, the amount of aluminum-based foreign matter may increase.

[0129] When the polyester resin (A) of the present invention is composed of at least one selected from polycarboxylic acids and their ester-forming derivatives and at least one selected from polyols and their ester-forming derivatives, the solution A1 in which the aluminum compound is dissolved is preferably a diol solution in which the aluminum compound is dissolved (hereinafter referred to as aluminum-containing diol solution A1), and the solution B1 in which the phosphorus compound is dissolved is preferably a diol solution in which the phosphorus compound is dissolved (hereinafter referred to as phosphorus-containing diol solution B1).

[0130] The maximum absorption wavelengths of aluminum-containing glycol solution A1 and phosphorus-containing glycol solution B1 will be explained below. By controlling the maximum absorption wavelengths of aluminum-containing glycol solution A1 and phosphorus-containing glycol solution B1 within a specific range, the polymerization activity can be stabilized, and a polyester resin of stable quality can be obtained. By controlling the maximum absorption wavelengths of aluminum-containing glycol solution A1 and phosphorus-containing glycol solution B1 within a specific range, the Lewis acid / base characteristics of aluminum-containing glycol solution A1 and phosphorus-containing glycol solution B1 can be controlled within a specific range. It is speculated that these Lewis acid / base characteristics will affect the complexation reaction between the aluminum compound and the phosphorus compound, and this complexation reaction will affect the polymerization activity.

[0131] <Maximum absorption wavelength of aluminum-containing glycol solution A1>

[0132] The aluminum-containing glycol solution A1 preferably has a maximum absorption wavelength of 562.0–572.0 nm, more preferably 567.0–572.0 nm. The maximum absorption wavelength of the aluminum-containing glycol solution A1 is obtained by measuring the absorption spectrum of the sample solution using a UV-Vis spectrophotometer after adding the acid dye Mordant Blue 13 to the aluminum-containing glycol solution A1. The detailed measurement method is described below.

[0133] Aluminum compounds and phosphorus compounds functionally form complexes with catalytic activity. To maximize polymerization activity, the alkalinity of the aluminum compounds contained in the aluminum-containing glycol solution A1 is preferably within a specific range.

[0134] The maximum absorption wavelength of the aluminum-containing glycol solution A1 can be affected by the type and amount of aluminum compound used, the type of glycol, and the temperature, pressure, and time during the preparation of the glycol solution. For example, preferred embodiments include using an aluminum compound with an aluminum content within a specific range, or processing the aqueous glycol solution in the aluminum-containing glycol solution A1 under reduced pressure or vacuum.

[0135] When the maximum absorption wavelength of the aluminum-containing glycol solution A1 is less than the above-mentioned range, the alkalinity of the aluminum compound in the solution decreases, making it unable to fully form a complex with the phosphorus compound, potentially leading to reduced polymerization activity and an increase in the amount of aluminum-based foreign matter. On the other hand, when the maximum absorption wavelength is greater than the above-mentioned range, there are technical difficulties.

[0136] <Maximum absorption wavelength of phosphorus-containing diol solution B1>

[0137] The maximum absorption wavelength of the phosphorus-containing glycol solution B1 is preferably 458.0–465.0 nm, more preferably 460.0–463.0 nm, and even more preferably 461.0–462.0 nm. The maximum absorption wavelength of the phosphorus-containing glycol solution B1 is obtained by measuring the absorption spectrum of the sample solution using a UV-Vis spectrophotometer after adding an aqueous solution of the basic dye Bismarck Brown to the phosphorus-containing glycol solution B1. Detailed measurement methods are described below.

[0138] Phosphorus compounds and aluminum compounds functionally form complexes with catalytic activity. To maximize polymerization activity, the acidity of the phosphorus compounds contained in the phosphorus-containing glycol solution B1 is preferably within a specific range.

[0139] The maximum absorption wavelength of the phosphorus-containing glycol solution B1 is affected by the type and amount of phosphorus compound used, the type of glycol, and the temperature, pressure, and time during solution preparation. When the maximum absorption wavelength of the phosphorus-containing glycol solution B1 is greater than the above range, the acidity of the phosphorus compound decreases, preventing it from fully forming a complex with the aluminum compound. This causes the phosphorus compound to distill out of the polymerization system, leading to an increase in aluminum-based foreign matter, which is not preferable. Conversely, when the maximum absorption wavelength is less than the above range, the acidity of the phosphorus compound increases, strengthening the bond with the aluminum compound, potentially resulting in a significant decrease in polymerization activity.

[0140] <Heat Treatment of Phosphorus Compounds>

[0141] Furthermore, the phosphorus compound used in this invention is preferably a product that has undergone heat treatment in a solvent. The solvent used is not limited to any solvent selected from the group consisting of water and alkylene glycols. As for the alkylene glycol, a solvent in which the phosphorus compound has been dissolved is preferred, and a glycol such as ethylene glycol, which is a component of the target polyester resin, is more preferably used. The heat treatment in the solvent is preferably performed from the point where the phosphorus compound dissolves, although incomplete dissolution is acceptable.

[0142] The heat treatment conditions described above are preferably a heat treatment temperature of 170–196°C, more preferably 175–185°C, and even more preferably 175–180°C. The heat treatment time is preferably 125–240 minutes, more preferably 140–210 minutes.

[0143] The concentration of phosphorus compound during the above heat treatment is preferably 3 to 10% by mass.

[0144] The above heat treatment can ensure that the acidity of the phosphorus compound in the glycol solution is constant. By using it in combination with aluminum compound, the polymerization activity can be improved while the amount of aluminum foreign matter generated by the polymerization catalyst can be reduced.

[0145] When using the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester of the phosphorus compound shown in (Formula 1) as the phosphorus compound, the structure of this part of the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester of the phosphorus compound shown in (Formula 1) changes during the aforementioned heat treatment. For example, changes occur such as the departure of the tert-butyl group, hydrolysis of the ethyl ester group, and the hydroxyethyl transesterification structure (transesterification structure with ethylene glycol). Therefore, in this invention, the phosphorus compound includes not only the 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester shown in (Formula 1) but also phosphorus compounds with structural changes. It should be noted that the departure of the tert-butyl group occurs significantly at the high temperature of the polymerization process.

[0146] The following examples illustrate nine phosphorus compounds in which a portion of diethyl 3,5-di-tert-butyl-4-hydroxybenzylphosphonate undergoes structural changes. The amounts of each phosphorus compound whose structure has changed in the diol solution can be quantified by P-NMR spectroscopy of that solution.

[0147]

Chemistry 2

[0148]

[0149] Therefore, the phosphorus compounds in this invention include, in addition to 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester, nine modified versions of 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid dialkyl ester as shown in the above chemical formula.

[0150] <Maximum absorption wavelength of the mixture of aluminum-containing glycol solution A1 and phosphorus-containing glycol solution B1>

[0151] The maximum absorption wavelength of the mixture of aluminum-containing glycol solution A1 and phosphorus-containing glycol solution B1 (hereinafter referred to as the "mixture") is preferably 559.0–560.9 nm, more preferably 559.5–560.8 nm, and even more preferably 559.7–560.6 nm. The maximum absorption wavelength of the mixture is obtained by measuring the absorption spectrum of the sample solution using a UV-Vis spectrophotometer after adding the acid dye Mordant Blue 13 to the mixture. Detailed measurement methods are described below.

[0152] By ensuring the maximum absorption wavelength of the mixture is within the aforementioned range, it is preferable to maintain a state that simultaneously enhances polymerization activity and suppresses aluminum-based foreign matter in the complexation reaction of the aluminum and phosphorus compounds. On the other hand, when the maximum absorption wavelength is greater than the aforementioned range, the alkalinity of the mixture increases. Since the polymerization system of polyester resin is acidic, if the mixture is added to the polymerization system, the aluminum compounds will neutralize the carboxyl termini of the polyester resin and become foreign, potentially increasing the amount of aluminum-based foreign matter. Conversely, when the maximum absorption wavelength is less than the aforementioned range, the alkalinity of the mixture is too low, the complexation of the aluminum and phosphorus compounds becomes too stable, and the polymerization activity may decrease.

[0153] For the polyester resin (A), the content of aluminum, which is equivalent to aluminum-based foreign matter, in the polyester resin (A) is preferably 3000 ppm by mass or less, more preferably 2800 ppm by mass or less. Aluminum-based foreign matter refers to aluminum compounds derived from the polymerization catalyst, which are insoluble in the polyester resin (A). If the content of aluminum-based foreign matter exceeds the above range, insoluble fine foreign matter will be generated in the polyester resin (A), which may lead to a deterioration in membrane quality. In addition, it also leads to increased filter clogging during the polycondensation process and the membrane forming process. The lower limit of the content of aluminum, which is equivalent to aluminum-based foreign matter, is preferably 0 ppm by mass, but due to technical difficulties, it is around 300 ppm by mass.

[0154] It should be noted that, as can be seen from the aluminum content measured by the measurement method described later in the embodiments in this specification, this index is only used to relatively evaluate the amount of aluminum-based foreign matter, and does not represent the absolute value of the amount of aluminum-based foreign matter contained in the polyester resin (A).

[0155] [Contains anti-blocking agent masterbatch (B)]

[0156] By using a masterbatch (B) containing an anti-blocking agent, during the film formation of the polyester resin composition manufactured in this invention, surface protrusions are formed on the surface of the resulting polyester film via the anti-blocking agent, thereby improving the film's slip properties, operational stability, abrasion resistance, roll-up properties, and other operational characteristics, thus enabling mixing.

[0157] Although the type of polyester resin constituting the masterbatch (B) is not limited, it is preferred to use the same polyester resin as the base polyester resin (A).

[0158] The volume average particle size of the anti-blocking agent contained in the masterbatch (B) is preferably 0.5–3.0 μm, more preferably 0.8–2.5 μm, and even more preferably 2.0–2.5 μm. When the volume average particle size of the anti-blocking agent is less than 0.5 μm, the effect on the membrane's slip properties, operational stability, and other operability may be reduced. On the other hand, when the volume average particle size of the anti-blocking agent is greater than 3.0 μm, the quality of the membrane may be impaired due to the formation of large protrusions. It should be noted that the volume average particle size of the anti-blocking agent can be obtained by measuring the particle size distribution using water or ethylene glycol as a medium, as detailed in the following description.

[0159] The content of the anti-blocking agent in the masterbatch (B) is preferably in the range of 0.5% to 20% by mass, more preferably in the range of 0.6% to 15% by mass. When it is less than 0.5% by mass, the masterbatch (B) requires a larger proportion, which becomes economically disadvantageous. Conversely, if it is greater than 20% by mass, the anti-blocking agent will agglomerate, resulting in an increase in coarse particles, which will cause clogging of the filter used to clarify the polymer in the film-forming process, and may lead to problems such as increased surface defects during film formation.

[0160] <Insoluble particles>

[0161] The masterbatch (B) preferably contains insoluble particles that are insoluble in the polyester resin (A). That is, the anti-blocking agent preferably contains insoluble particles that are insoluble in the polyester resin (A). The volume average particle size of these insoluble particles is 0.5–3.0 μm, and the content of these insoluble particles is more preferably 0.5–20% by mass. The insoluble particles used in this invention are not particularly limited as long as they are insoluble in the polyester resin (A), and can be inorganic or organic particles. Alternatively, they can be a composite of inorganic and organic particles.

[0162] The types of inorganic particles are not particularly limited. For example, oxides, carbonates, silicates, sulfates, and aluminates of metals such as titanium, aluminum, silicon, calcium, magnesium, and barium can be listed.

[0163] Specifically, in addition to titanium dioxide, aluminum oxide, aluminosilicate, silicon dioxide, calcium oxide, calcium carbonate, barium sulfate, etc., naturally sourced talc, mica, kaolinite, zeolite, etc., can also be listed as types of inorganic particles, but they are not limited to these.

[0164] The types of organic particles are not particularly limited, but can be listed as silicone-based, cross-linked polyacrylic acid-based, benzoguanamine resin-based, etc.

[0165] When the insoluble particles are silica particles, a highly transparent polyester film can be obtained, which is therefore preferred.

[0166] [Manufacturing method of masterbatch (B)]

[0167] There are no particular limitations on the manufacturing method of masterbatch (B). For example, it can be a polymerization process addition method in which an anti-blocking agent slurry is added during the polymerization process of polyester resin, or a so-called melt mixing method in which polyester resin is mixed with the anti-blocking agent in a molten state.

[0168] <Addition Method in Polymerization Process>

[0169] There is no limitation on the timing of adding the anti-blocking agent slurry in the polymerization process. It can be added at any time from the initial stage of the transesterification or esterification reaction to the start of the initial polymerization. It can also be added directly to the reaction tank, or added using a mixer to the conveying pipeline between the reaction tanks. Alternatively, an addition tank can be set up for addition.

[0170] In addition, to prevent the anti-blocking agent from agglomerating, it is preferable to use glycol-based slurries, followed by mechanical dispersion using a media stirring disperser such as a sand mill, grinding mill, or ultrasonic mill, and then add alkali metal compounds, ammonium compounds, or phosphorus compounds to improve the dispersion efficiency before adding them.

[0171] The amount of anti-blocking agent added in the above polymerization process is preferably 0.5 to 2.0% by mass, more preferably 0.6 to 1.8% by mass. If it is less than 0.5% by mass, the formation of coarse particles increases due to the aggregation of the diluted anti-blocking agent. In addition, if it is greater than 2.0% by mass, the effect of preventing coarse particles is insufficient, and foreign matter may be generated when it is used as a membrane.

[0172] <Melting and Mixing Method>

[0173] There are no restrictions on the method of melt mixing. Single-screw or multi-screw mixers can be used, as well as kneaders.

[0174] The amount of anti-blocking agent added in the above melt mixing method is preferably 2.0 to 20% by mass, more preferably 3.0 to 15% by mass, relative to the polyester resin used in the masterbatch (B). When the amount of anti-blocking agent added is less than 2.0% by mass or greater than 20% by mass, the dispersibility of the anti-blocking agent with respect to the polyester resin is poor, and the coarse particles of the anti-blocking agent agglomerates may increase.

[0175] The above-mentioned melt mixing method can be carried out after the polyester resin is melted, or it can be carried out by installing a mixing device at the outlet of the polyester resin polymerization process.

[0176] The polymerization catalyst of the polyester resin used in masterbatch (B) is not limited, but it is preferably the same as the catalyst used in the manufacture of polyester resin (A). That is, the polyester resin used in masterbatch (B) is preferably manufactured using a polymerization catalyst composed of aluminum compounds and phosphorus compounds.

[0177] [Masterbatch containing electrostatic adhesion promoter (C)]

[0178] If a polyester resin composition containing a masterbatch (C) (hereinafter sometimes referred to as "masterbatch (C)") containing an electrostatic adhesion promoter is film-formed, electrostatic adhesion to the cooling drum of the sheet can be improved in the electrostatic adhesion casting process, thereby improving the productivity of the film and reducing film thickness unevenness. As a result, the productivity and quality of the polyester film can be improved.

[0179] The type of polyester resin constituting the masterbatch (C) is not limited, but it is preferably the same polyester resin as the polyester resin (A).

[0180] The melt resistivity of the masterbatch (C) is preferably 0.005 × 10⁻⁶. 8 ~0.05×10 8 Ω·cm, more preferably 0.005×10 8 ~0.025×10 8 Ω·cm. The melt resistivity of the masterbatch is 0.05×10 Ω·cm. 8 At higher Ω·cm values, a large amount of masterbatch (C) needs to be added to improve the film-forming properties of the polyester resin composition, which leads to increased manufacturing costs. Technically, it is difficult to achieve a melt resistivity of masterbatch (C) less than 0.005 × 10⁻⁶. 8 Ω·cm.

[0181] Furthermore, to improve the film-forming properties of polyester films, the melt resistivity of polyester films formed from polyester resin compositions mixed with masterbatch (C) is preferably 0.1 × 10⁻⁶. 8 ~0.3×10 8 Ω·cm, more preferably 0.15×10 8 ~0.25×10 8Ω·cm. The molten resistivity can be determined by the method described in the following examples.

[0182] In the masterbatch (C), magnesium compounds or alkali metal compounds are preferably added to reduce melt resistivity. Furthermore, to prevent these metal ions from being indiscriminately dispersed in the polyester resin composition and to further improve thermal stability, phosphorus compounds are preferably added. The masterbatch (C) preferably contains 400–2700 ppm by mass of magnesium, 40–270 ppm by mass of alkali metals, and 200–1700 ppm by mass of phosphorus.

[0183] As the magnesium compound used in this invention, known magnesium compounds can be used. For example, lower fatty acid salts such as magnesium acetate and alkoxides such as magnesium methoxide can be used, either individually or in combination of two or more. Magnesium acetate is particularly preferred.

[0184] The masterbatch (C) preferably contains 400 to 2700 ppm by mass of magnesium. When the amount of magnesium is less than 400 ppm by mass, the melt resistivity becomes high. To improve the film-forming properties of the polyester resin composition, a large amount of masterbatch (C) needs to be added, resulting in problems such as low efficiency as a masterbatch and increased manufacturing costs. When the amount of magnesium is greater than 2700 ppm by mass, the amount of insoluble foreign matter (magnesium salt) generated increases. In addition, it may lead to reduced heat resistance and poor film coloring. The amount of magnesium is more preferably 450 to 2500 ppm by mass, and even more preferably 450 to 2000 ppm by mass.

[0185] The alkali metal contained in the masterbatch (C) can be, for example, lithium, sodium, and potassium. Other alkali metal compounds can include, for example, lower fatty acid salts with 2 to 4 carbon atoms such as lithium acetate and potassium acetate, and alkoxides such as potassium methoxide; any one of these can be used alone, or two or more can be used in combination. Potassium is preferred because it has a significant effect on reducing melt resistivity. As an alkali metal compound, lower fatty acid salts with 2 to 4 carbon atoms are preferred, alkali metal acetates are more preferred, and potassium acetate is even more preferred.

[0186] The masterbatch (C) preferably contains 40 to 270 ppm by mass of alkali metal elements. When the amount of alkali metal elements is less than 40 ppm by mass, the melt resistivity becomes high. To improve the film-forming properties of the polyester resin composition, a large amount of masterbatch (C) needs to be added, which may lead to problems such as low efficiency and increased manufacturing costs. When the amount of alkali metal elements is greater than 270 ppm by mass, the effect of improving melt resistivity becomes saturated, and it may also lead to reduced heat resistance and poor film coloring. The amount of alkali metal elements is more preferably 45 to 250 ppm by mass, and even more preferably 45 to 200 ppm by mass.

[0187] Examples of phosphorus compounds contained in the masterbatch (C) include phosphoric acid, phosphorous acid, hypophosphorous acid, phosphonic acid, and their ester compounds. Examples include phosphoric acid, trimethyl phosphate, tributyl phosphate, triphenyl phosphate, monomethyl phosphate, dimethyl phosphate, monobutyl phosphate, dibutyl phosphate, phosphorous acid, trimethyl phosphite, tributyl phosphite, methylphosphonic acid, dimethyl methylphosphonate, dimethyl ethyl phosphonate, diethyl phenylphosphonate, diphenyl phenylphosphonate, triethyl phosphonoacetate, hypophosphonic acid, methyl hypophosphonic acid, dimethyl hypophosphonic acid, phenyl hypophosphonic acid, diphenyl hypophosphonic acid, methyl dimethyl phosphonate, diphenyl hypophosphonate, etc. To significantly demonstrate the effects of the present invention, it is preferable to select at least one from the group consisting of trialkyl phosphates and triethyl phosphonoacetate, more preferably trialkyl phosphates. In trialkyl phosphate esters, it is further preferred that at least one of the alkyl groups in the alkyl ester is an alkyl group having 2 to 4 carbon atoms, and it is particularly preferred that all the alkyl groups in the alkyl ester are alkyl groups having 2 to 4 carbon atoms. Examples of particularly preferred phosphorus compounds include triethyl phosphate, tripropyl phosphate, and tributyl phosphate; any one of these can be used alone, or two or more can be used in combination. Triethyl phosphate is particularly preferred because it forms a complex with magnesium ions of appropriate strength, resulting in a masterbatch (C) with low melt resistivity, few impurities, and excellent color.

[0188] The masterbatch (C) preferably contains 200–1700 ppm by mass of phosphorus. When the amount of phosphorus is less than 200 ppm by mass, magnesium ions and alkali metal ions are stabilized, and due to the reduced dispersion effect in the polyester resin composition, the amount of insoluble magnesium-based foreign matter generated may increase. Furthermore, since the foreignized magnesium loses its effect of reducing melt resistivity, the melt resistivity may increase. In addition, it may lead to reduced heat resistance and poor film coloring. If the amount of phosphorus is greater than 1700 ppm by mass, due to the interaction of excess phosphorus compounds with magnesium ions, the charge of magnesium ions does not contribute to the effect of reducing melt resistivity, and the melt resistivity may increase even if a large amount of magnesium is added. More preferably, the amount of phosphorus is 220–1000 ppm by mass.

[0189] The content of magnesium, alkali metal, and phosphorus elements in the masterbatch (C) can be quantified by the method described in the following examples. There is no particular limitation on the timing of adding the magnesium, alkali metal, and phosphorus compounds to the polyester resin used in the masterbatch (C). Adding them during the polymerization of the polyester, particularly during the esterification (or transesterification) process, or between the end of the esterification (or transesterification) process and the start of the polycondensation process, can suppress the formation of salts between the acid components of the polyester and magnesium and alkali metal ions, thus preventing foreignization. Furthermore, it allows for uniform dispersion in the oligomer, which is therefore preferable.

[0190] When these compounds are added during polyester polymerization, the amount of magnesium and alkali metal elements added is almost directly retained in the polyester resin composition, but phosphorus will distill out of the polymerization system under reduced pressure. Therefore, it is necessary to determine the amount of phosphorus compound to be added based on a prior understanding of the relationship between the amount added and the amount retained.

[0191] When the polyester resin used in the masterbatch (C) is a polyester resin with dicarboxylic acid and diol as constituent components, and the amount of magnesium relative to the dicarboxylic acid is set to m mol%, the amount of alkali metal is set to k mol%, and the amount of phosphorus is set to p mol%, the effects of the present invention can be obtained by satisfying the following formula (4).

[0192] (4) 2≤(m+k / 2) / p≤3.5

[0193] Phosphorus atoms are believed to stabilize magnesium ions and alkali metal ions without alienation. Since magnesium ions have a valence of 2 and alkali metal ions have a valence of 1, the sum of the amounts of magnesium ions and alkali metal ions is expressed as (m+k / 2). The ratio (m+k / 2) / p is used to represent the relative amounts of magnesium ions and alkali metal ions relative to phosphorus atoms.

[0194] When the value of (m+k / 2) / p is greater than 3.5, the amount of phosphorus is relatively small compared to magnesium and alkali metals, resulting in the stabilization of magnesium and alkali metal ions and a decreased dispersion effect in the polyester resin composition, leading to an increase in the formation of insoluble foreign matter (magnesium salts, alkali metal salts). Furthermore, since the foreignized magnesium loses its effect of reducing melt resistivity, the melt resistivity becomes higher relative to the amount of magnesium added. In addition, this leads to a decrease in heat resistance and a deterioration in the color tone of the masterbatch (C) and the film.

[0195] When the value of (m+k / 2) / p is less than 2, the amount of phosphorus becomes relatively excessive relative to magnesium and alkali metals. Although the interaction between the excess phosphorus compound and magnesium ions improves the color reduction, the charge of the magnesium ions does not contribute to the reduction of melt resistivity, resulting in a higher melt resistivity relative to the amount of magnesium added. (m+k / 2) / p is more preferably 2.3 or more and 3 or less, and even more preferably 2.5 or more and 3 or less.

[0196] That is, the effect of reducing molten resistivity and color tone are contradictory. Therefore, by satisfying equation (4), it is possible to have both the effect of reducing molten resistivity and color tone.

[0197] There are no limitations on the polymerization catalyst of the polyester resin used in the masterbatch (C), but it is preferable to use the same catalyst as that used in the manufacture of the polyester resin (A). It should be noted that since the compound used as an electrostatic adhesion promoter also acts as a co-catalyst, the catalyst used in the manufacture of the polyester resin (A) may not use a phosphorus compound, that is, it may only use an aluminum compound.

[0198] [Anti-blocking agent / electrostatic adhesion promoter composite masterbatch (D)]

[0199] In this invention, the anti-blocking agent / electrostatic adhesion promoter composite masterbatch (D) (hereinafter referred to as "composite masterbatch (D)" or "masterbatch (D)") combines the composition and characteristics of both the anti-blocking agent masterbatch (B) and the electrostatic adhesion promoter masterbatch (C). Therefore, masterbatch (D) can be mixed with the matrix polyester resin (A) instead of masterbatch (B). By using a polyester resin composition that mixes composite masterbatch (D) and polyester resin (A), the electrostatic adhesion can be improved when manufacturing a polyester film by forming a film from the polyester resin composition, just as it can be with a polyester resin composition that mixes polyester resin (A) and masterbatch (B) and masterbatch (C), thereby improving the productivity of the polyester film. Furthermore, by forming surface protrusions on the surface of the obtained polyester film via the anti-blocking agent, the film's slip properties, operational stability, abrasion resistance, and roll-up properties can be improved.

[0200] The composite masterbatch (D) contains insoluble particles that are insoluble in the polyester resin (A), wherein the volume average particle size of the insoluble particles is 0.5 to 3.0 μm, and the content of the insoluble particles is preferably 0.5 to 20% by mass. In addition, the composite masterbatch (D) preferably contains 400 to 2700 ppm by mass of magnesium, 40 to 270 ppm by mass of alkali metals, and 200 to 1700 ppm by mass of phosphorus.

[0201] The volume average particle size and content of the anti-blocking agent contained in the composite masterbatch (D) are preferably within the same range as those of the anti-blocking agent in the masterbatch (B), for the same reasons as those stated in the masterbatch (B) section.

[0202] The content of magnesium, alkali metals and phosphorus in the composite masterbatch (D) is preferably within the same range as that in the masterbatch (C), for the same reasons as those stated in the masterbatch (C) section.

[0203] The content of magnesium, alkali metal, and phosphorus elements in the composite masterbatch (D) is the same as that in the masterbatch (C), and can be quantitatively determined by the method described in the following examples. There is no particular limitation on the timing of adding the magnesium compound, alkali metal compound, and phosphorus compound to the polyester resin used in the composite masterbatch (D). Adding them during polyester polymerization, particularly during the esterification (or transesterification) process, or between the end of the esterification (or transesterification) process and the start of the polycondensation process, is preferred because it can suppress the formation of salts between the acid components of the polyester and magnesium and alkali metal ions, thus preventing foreignization, and also allows for uniform dispersion in the oligomers.

[0204] When these compounds are added during the polymerization of polyester, the amount of magnesium and alkali metal elements added is almost directly retained in the polyester resin composition, while phosphorus is distilled out of the polymerization system under reduced pressure. Therefore, the amount of phosphorus compound added needs to be determined based on the relationship between the amount added and the amount retained.

[0205] When the polyester resin used in the composite masterbatch (D) is a polyester resin with dicarboxylic acid and diol as constituent components, and the amount of magnesium atoms relative to the dicarboxylic acid component is set as m (mol%), the amount of alkali metal atoms is set as k (mol%), and the amount of phosphorus atoms is set as p (mol%), the effects of the present invention can be obtained by satisfying the above formula (4) in the molar ratio of magnesium atoms, alkali metal atoms, and phosphorus atoms. The reason is the same as that described in the masterbatch (C) section.

[0206] There are no limitations on the polymerization catalyst of the polyester resin used in the composite masterbatch (D), but it is preferable to use the same catalyst as that used in the manufacture of the polyester resin (A). It should be noted that since the compound used as an electrostatic adhesion promoter also acts as a cocatalyst, phosphorus compounds may not be used in the catalyst used in the manufacture of the polyester resin (A), i.e., only aluminum compounds may be used.

[0207] There are no particular limitations on the manufacturing method of the composite masterbatch (D). For example, in the manufacturing process of the polyester resin used in the composite masterbatch (D), an anti-blocking agent slurry solution and the components of the aforementioned masterbatch (C) may be added, or the masterbatch (B) and masterbatch (C) may be melt-blended. In addition, in the manufacturing process of the polyester resin used in the composite masterbatch (D), an anti-blocking agent and an electrostatic adhesion promoter may also be added.

[0208] [other]

[0209] The polyester resin composition used in this invention preferably does not contain resins other than polyester resin, but may contain resins other than polyester resin without prejudice to the purpose of this invention. Resins other than polyester resin are not particularly limited, and examples include polyolefin resins, polyamide resins, and polyacetal resins. The resins other than polyester resin in the polyester resin composition are preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less, particularly preferably 3% by mass or less, and most preferably 1% by mass or less. The method of mixing the above-mentioned resins into the polyester resin is not particularly limited; for example, methods such as adding them during the polyester resin manufacturing process or dry mixing with the manufactured polyester resin to obtain uniformly can be included.

[0210] The polyester resin composition used in this invention may, depending on the intended use, contain one or more of the following additives: diethylene glycol inhibitors, fluorescent whitening agents, colorants such as dyes and pigments, UV protectants, infrared absorbing pigments, heat stabilizers, surfactants, and antioxidants, among others. As diethylene glycol inhibitors, basic compounds such as alkylamine compounds or ammonium salt compounds may be used; as antioxidants, aromatic amines, phenols, and other antioxidants may be used; and as stabilizers, sulfur-based and amine-based stabilizers may be used. These additives are preferably added at a ratio of 10% by mass or less relative to the polyester resin composition, more preferably at a ratio of 5% by mass or less.

[0211] [Polyester film]

[0212] A polyester film can be obtained by forming a polyester resin composition obtained by the manufacturing method of the present invention. The polyester film can be a single-layer structure or a multilayer structure having two or more layers.

[0213] The single-layer polyester film is preferably formed from a polyester resin composition containing a mixture of polyester resin (A) and masterbatch (B). More preferably, the film contains 500 to 2000 ppm by mass of insoluble particles and has a melt resistivity of 0.15 to 0.6 × 10⁻⁶. 8 A single-layer polyester film formed by mixing a polyester resin composition (A) and masterbatch (B) and masterbatch (C) in an Ω·cm manner, or a single-layer polyester film formed by mixing a polyester resin composition (A) and composite masterbatch (D).

[0214] The content of insoluble particles in the single-layer polyester film is more preferably 600 to 1800 ppm by mass. Furthermore, the melt resistivity of the single-layer polyester film is more preferably 0.15 to 0.4 × 10⁻⁶. 8 Ω·cm.

[0215] In a multilayer polyester film, the composition of each layer can be changed to achieve the above-mentioned properties, or all layers can have the same composition.

[0216] For example, when the polyester film has a three-layer structure of surface layer A / intermediate layer / surface layer B, it is preferable that at least one (preferably both) of the polyester compositions forming surface layer A and surface layer B contains an anti-blocking agent, while the polyester composition forming the intermediate layer does not contain it. If the anti-blocking agent is present on the surface of the polyester film, it forms surface protrusions on the surface of the polyester film, which improves the film's slip properties, operational stability, abrasion resistance, and roll-up properties. If the anti-blocking agent is mixed in both of the polyester compositions forming surface layer A and surface layer B, the mixing effect of the anti-blocking agent becomes significant, which is more preferable. On the other hand, mixing the anti-blocking agent into the polyester composition forming the intermediate layer is not necessary; rather, by not mixing the anti-blocking agent into the polyester composition forming the intermediate layer, the reduction in film transparency caused by the anti-blocking agent is suppressed, and the transparency of the resulting film can be significantly improved, which is therefore preferred.

[0217] Even in multilayer polyester films, from the viewpoint of improving electrostatic adhesion, it is preferable to mix masterbatch (C) or composite masterbatch containing electrostatic adhesion promoters throughout the entire layer.

[0218] The number of layers and the thickness ratio are not limited in the multilayer structure, but a 3-layer structure is preferred, and the thickness ratio of the surface layer / intermediate layer / surface layer is 0.05 / 0.9 / 0.05 to 0.2 / 0.6 / 0.2. By making the film a 3-layer structure as described above, the film has high transparency and the thickness unevenness of the film can be reduced.

[0219] When using recycled polyester resin recovered from membrane manufacturing debris such as the cut portions and defective portions at both ends of the membrane generated during the membrane manufacturing process, in the above-mentioned three-layer membrane structure, by mixing the recycled polyester resin recovered from the cut portions and defective portions at both ends of the membrane generated during the membrane manufacturing process into the middle layer, it is possible to suppress the occurrence of membrane surface defects caused by foreign matter mixed in the cut portions and recycled polyester resin.

[0220] In the case of the above-described three-layer structure film, it is preferable to melt-extrude a polyester resin composition in which polyester resin (A) and masterbatch (B) are mixed, such that the content of insoluble particles in one side (preferably both sides) is 500 to 2000 ppm by mass. More preferably, the content of insoluble particles in the surface layer is 600 to 1800 ppm by mass. Alternatively, a composite masterbatch (D) can be used instead of masterbatch (B). By using composite masterbatch (D), the transparency of the polyester film can be improved, and the economy can be enhanced.

[0221] In the case of the above-mentioned three-layer membrane structure, the preferred membrane resistivity is 0.15 to 0.6 × 10⁻⁶. 8Ω·cm. It is preferable to incorporate the masterbatch (C) into the polyester resin composition forming any layer so that the melt resistivity of the film is within the above-mentioned range. However, a composite masterbatch (D) may be used instead of the masterbatch (C). A melt resistivity of 0.15 to 0.4 × 10⁻⁶ is more preferably found in the film. 8 Ω·cm.

[0222] This application claims priority to Japanese Patent Application No. 2020-153075, filed on September 11, 2020. The entire contents of the description of Japanese Patent Application No. 2020-153075, filed on September 11, 2020, are incorporated herein by reference.

[0223]

Example

[0224] The present invention will be described below through embodiments, but the present invention is not limited to these embodiments. It should be noted that the evaluation methods used in each embodiment and comparative example are as follows.

[0225] [Evaluation Method]

[0226] (1) Maximum absorption wavelength of aluminum-containing ethylene glycol solution a1

[0227] Add 4 mL of ethylene glycol and 0.3 mL of 1 mmol / L Mordant Blue 13 aqueous solution to a 6 mL sample vial, then add 0.1 mL of the aluminum-containing ethylene glycol solution a1 (described later). Cover the vial and shake to mix for 10 seconds until the solution is homogeneous. After allowing it to stand at room temperature (23°C) for 10 minutes, use a UV-Vis spectrophotometer to measure the absorption spectrum of the sample solution under the following conditions, and determine the maximum absorption wavelength of the aluminum-containing ethylene glycol solution a1. It should be noted that in this determination, room temperature refers to 15–30°C, and all operations were performed indoors within this temperature range.

[0228] Apparatus: Shimadzu UV-1800 UV-Vis spectrophotometer (manufactured by Shimadzu Corporation)

[0229] Spectral bandwidth: 1nm

[0230] Sample slot: Square slot (Material: Polymethyl methacrylate (PMMA), Optical path length: 10mm)

[0231] Control solution: ethylene glycol

[0232] Scan range: 400–700 nm

[0233] Scan speed setting: 0.05 sec

[0234] Scanning pitch: 0.2nm

[0235] Number of scans: 1

[0236] (2) Maximum absorption wavelengths of phosphorus-containing ethylene glycol solutions b1 and b1'

[0237] Add 4 mL of ethylene glycol and 0.3 mL of a 1 mmol / L aniline brown aqueous solution to a 6 mL sample vial, then add 0.1 mL of phosphorus-containing ethylene glycol solution b1. Cover the vial and shake to mix for 10 seconds until the solution is homogeneous. After allowing it to stand at room temperature (23℃) for 10 minutes, use a UV-Vis spectrophotometer to measure the absorption spectrum of the sample solution under the following conditions, and determine the maximum absorption wavelength of the phosphorus-containing ethylene glycol solution b1. It should be noted that in this determination, room temperature refers to 15–30℃, and all operations were performed indoors within this temperature range.

[0238] Apparatus: Shimadzu UV-1800 UV-Vis spectrophotometer (manufactured by Shimadzu Corporation)

[0239] Spectral bandwidth: 1nm

[0240] Sample slot: Square slot (Material: PMMA, Optical path length: 10mm)

[0241] Control solution: ethylene glycol

[0242] Scan range: 400–700 nm

[0243] Scan speed setting: 0.05 sec

[0244] Scanning pitch: 0.2nm

[0245] Number of scans: 1

[0246] In addition, except for changing the phosphorus-containing ethylene glycol solution b1 to the phosphorus-containing ethylene glycol solution b1', the maximum absorption wavelength of the phosphorus-containing ethylene glycol solution b1' was determined using the same evaluation method as described above.

[0247] (3) The maximum absorption wavelength of the mixture of aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1 or b1'

[0248] Add 4 mL of ethylene glycol and 0.3 mL of 1 mmol / L Mordant Blue 13 aqueous solution to a 6 mL sample vial. Then add 0.1 mL of a mixture of aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1 or b1'. Cover the vial and shake to mix for 10 seconds until the solution is homogeneous. After standing at room temperature (23°C) for 10 minutes, use a UV-Vis spectrophotometer to measure the absorption spectrum of the sample solution under the following conditions and determine the maximum absorption wavelength. The mixing ratio of aluminum-containing ethylene glycol solution a1 to phosphorus-containing ethylene glycol solution b1 or b1' in the above mixture is the same as the mixing ratio of aluminum-containing ethylene glycol solution a1 to phosphorus-containing ethylene glycol solution b1 or b1' in each example. It should be noted that in this determination, room temperature refers to 15–30°C, and all operations are performed indoors within this temperature range.

[0249] Apparatus: Shimadzu UV-1800 UV-Vis spectrophotometer (manufactured by Shimadzu Corporation)

[0250] Spectral bandwidth: 1nm

[0251] Sample slot: Square slot (Material: PMMA, Optical path length: 10mm)

[0252] Control solution: ethylene glycol

[0253] Scan range: 400–700 nm

[0254] Scan speed setting: 0.05 sec

[0255] Scanning pitch: 0.2nm

[0256] Number of scans: 1

[0257] (4) Volume average particle size of silica particles

[0258] The particle size distribution was measured using a laser scattering particle size analyzer (Leeds & Northrup, Microtrac HRA model: 9320-X100), by diluting an ethylene glycol slurry of silica particles with water to essentially create an aqueous system. The volume average particle size was determined as the cumulative 50% of the measured particle size.

[0259] (5) Intrinsic viscosity (IV) of polyester resin (A), masterbatch (C) and masterbatch (D)

[0260] Polyester resin (A) was dissolved in a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (3 / 2 by mass) and the viscosity was measured at 30°C. The intrinsic viscosities of masterbatch (C) and masterbatch (D) were also measured using the same method as the intrinsic viscosity of polyester resin (A).

[0261] (6) Aluminum content in polyester resin (A) and masterbatch (C)

[0262] Polyester resin (A) was weighed in a platinum crucible, carbonized in an electric furnace, and then ashed in a muffle furnace at 550°C for 8 hours. The ashed sample was dissolved in 1.2M hydrochloric acid to prepare a sample solution. The concentration of aluminum in the polyester resin was determined by high-frequency inductively coupled plasma atomic emission spectrometry (ICP-AES).

[0263] Device: SPECTRO CIROS-120

[0264] Plasma power: 1400W

[0265] Plasma gas: 13.0 L / min

[0266] Assist gas: 2.0 L / min

[0267] Atomizer: Cross Atomizer

[0268] Fog chamber: Cyclone chamber

[0269] Measurement wavelength: 167.078nm

[0270] In addition, the concentration of aluminum in the masterbatch (C) was determined using the same method as that used for the polyester resin (A).

[0271] (7) Phosphorus content in polyester resin (A)

[0272] Polyester resin (A) was wet-decomposed under sulfuric acid, nitric acid, and perchloric acid, and then neutralized with ammonia. Ammonium molybdate and hydrazine sulfate were added to the adjusted solution, and the absorbance at 830 nm was measured using a UV-Vis spectrophotometer (Shimadzu UV-1700). The phosphorus concentration in polyester resin (A) was determined using a pre-prepared calibration curve.

[0273] (8) Aluminum-based foreign matter quantity

[0274] 30g of polyester resin (A) and 250mL of a 3 / 1 (mass ratio) mixed solution of p-chlorophenol and tetrachloroethane were placed in a 500mL Erlenmeyer flask with a stir bar added. The solution was heated and stirred at 100–105°C for 1.5 hours to dissolve the impurities. The solution was then filtered through a 47mm diameter, 1.0μm pore size polytetrafluoroethylene (PTFE) membrane filter (Advantec, product name: T100A047A). The effective filter diameter was 37.5mm. After filtration, the filter was washed with 50mL of chloroform and then dried.

[0275] The aluminum content of the membrane filter was quantified using a scanning X-ray fluorescence spectrometer (RIGAKU, ZSX100e, Rh tube 4.0kW). Quantification was performed on the central 30mm diameter section of the membrane filter. It should be noted that the calibration curve for this X-ray fluorescence analysis was obtained using polyethylene terephthalate resin with a known aluminum content, and the apparent aluminum content is expressed in ppm. The determination was performed at X-ray power of 50kV-70mA, using pentaerythritol as the spectroscopic crystal and a PC (proportional counter) as the detector, under PHA (pulse height analyzer) conditions of 100-300, measuring the intensity of Al-Kα rays. The calibration curve was used to quantify the aluminum content in the PET resin using high-frequency inductively coupled plasma atomic emission spectrometry.

[0276] (9) Back pressure rise coefficient (k)

[0277] Polyester resin (A) was vacuum dried at 140°C for 16 hours, then fed to a melt extruder. The extruder outlet pressure was controlled at 1.96 MPa, and a filter with a diameter of [missing information] was used. The filter was subjected to a spinning test at a spinning temperature of 295°C and a discharge rate of 6 g / min for 4 hours. During the spinning test, the filter pressure was recorded every 30 minutes. The back pressure rise per unit time ΔP (MPa / hour) was calculated using the pressure (MPa) after 4 hours from the start of spinning and the pressure (MPa) at the start of spinning.

[0278] The spinning nozzle uses a nozzle with 12 orifices. The nozzle has an orifice with a length of 0.3 mm. The filter uses a structure along the extruder outlet side with a 100-mesh metal mesh, a 10μm NASLON filter, a 100-mesh metal mesh, and a 50-mesh metal mesh.

[0279] The back pressure rise coefficient k is based on the back pressure rise per unit time ΔP (MPa / hour), flow rate Q (kg / hour), and filter area S (cm²). 2 It is calculated using the following formula.

[0280] k = ΔP / (Q / S)

[0281] The area S is calculated based on the filter diameter, and the flow rate Q is calculated from the discharge rate.

[0282] (10) Hue (Co-b)

[0283] Co-b was measured using a colorimeter (Nippon Denko Kogyo Co., Ltd., ZE-6000) based on the tristimulus values ​​XYZ of the basic stimulus amount of the color. The higher the Co-b value, the stronger the yellow odor.

[0284] (11) Number of coarse particles in masterbatch (B)

[0285] Polyester resin sheets were prepared by diluting and mixing SiO2 particles with polyester resin (A) at a rate of 0.12% by mass relative to the masterbatch (B). One sheet was sandwiched between two glass slides (Matsunami Micro slides, 25mm × 25mm, 0.2mm thick) and heated to approximately 300°C on a hot plate until melted, pressed to a thickness of 0.8–0.9mm, and immediately rapidly cooled as a sample for observation. The central portion of the sample thickness was observed using a phase contrast microscope (Nikon OPTIPHOT) and an objective lens (same company, 10x magnification, 0.5 aperture). Images were imported from a CCD camera into an image analysis device (Nilike LUZEX AP) for image analysis, and the number of particles larger than 10μm was calculated. The same measurement was performed 20 times with different viewing angles to determine the total number of particles, and the number of particles per 1mm was calculated. 2 The number of particles with a diameter of 10 μm or larger in the viewing area is defined as the number of coarse particles.

[0286] In addition, the number of coarse particles for composite masterbatch (D) is determined using the same method as for masterbatch (B).

[0287] (12) The content (residual amount) of magnesium, potassium and phosphorus in the masterbatch (C)

[0288] Masterbatch (C) was heated to its melting point +20°C within a 5mm thick stainless steel ring with an inner diameter to create a sample slide. The elemental amounts were determined by X-ray fluorescence analysis, expressed in ppm (mass standard). It should be noted that for quantification, a calibration curve based on a sample with pre-known elemental amounts was used.

[0289] (13) Molten resistivity (ρi)

[0290] Two electrodes (0.6 mm diameter stainless steel wires) were placed at both ends of the composition used in the film fabrication of Example 11 (hereinafter referred to as the film fabrication composition) which was melted at 275°C. The composition and the two electrodes were clamped between two quartz plates with a width of 2 cm to form a uniform film fabrication composition layer with a width of 2 cm and a thickness of 0.6 mm. The current (io) when a DC voltage of 120 V was applied was measured at a temperature of 280°C, and the melt resistivity value ρi (Ω·cm) was calculated using the following formula. In addition, the melt resistivity was also calculated for the film fabrication compositions, masterbatch (C), and composite masterbatch (D) of Examples 12 to 14 and Comparative Example 11.

[0291] ρi(Ω·cm)=(A / L)×(V / io)

[0292] [A: Electrode area (cm²)] 2 L: Electrode spacing (cm), V: Voltage (V), io: Current (A)

[0293] A(cm 2 = [width of the molten film-forming composition layer] × [thickness] = 2 (cm) × 0.06 (cm), V = 120 (V). L is the measured value of the diameter without the electrode, which is 1.3 cm.

[0294] (14) Electrostatic adhesion of the membrane composition

[0295] Using the film-making compositions of Examples 11-14 and Comparative Example 11, tungsten wire electrodes were placed between the die head and the cooling drum of an extruder. A voltage of 10-15 kV was applied between the electrodes and the casting drum for casting. The surface of the resulting cast sheet was observed with the naked eye, and the casting speed at which pinner bubbles began to form was evaluated. The higher the casting speed, the better the electrostatic adhesion of the polymer.

[0296] (15) Static friction coefficient of polyester film (μs)

[0297] Two polyester films from Example 11 were prepared, and the static friction coefficient (μs) was determined using a tensile testing machine (TENSILON RTG-1210, A&D Corporation) when one polyester film was bonded to the other at 23°C and 65% RH, based on JIS K-7125. The static friction coefficients of the films from Examples 12-14 and Comparative Example 11 were also determined using the same method.

[0298] The following describes the preparation of aluminum-containing glycol solutions, the preparation of phosphorus-containing glycol solutions, and the manufacture of polyester resin (A), various masterbatches (B) to (D), and films.

[0299] (1) Preparation of aluminum-containing ethylene glycol solution a1

[0300] A 20 g / L aqueous solution of basic aluminum acetate was added to a mixing vessel along with an equal volume of ethylene glycol. The mixture was stirred at room temperature (23°C) for several hours, then stirred under reduced pressure (3 kPa) at 50–90°C for several hours to distill off water, thus preparing a 20 g / L aluminum-containing ethylene glycol solution a1. The maximum absorption wavelength of the aluminum-containing ethylene glycol solution a1 was 571.6 nm.

[0301] (2) Preparation of phosphorus-containing ethylene glycol solutions b1 and b1'

[0302] <Phosphorus-containing ethylene glycol solution b1>

[0303] Irganox 1222 (manufactured by BASF), a phosphorus compound, was added to a mixing tank along with ethylene glycol. The mixture was then heat-treated at 175°C for 150 minutes under nitrogen purging with stirring to prepare a phosphorus-containing ethylene glycol solution b1 containing 50 g / L of the phosphorus compound. The maximum absorption wavelength of the phosphorus-containing ethylene glycol solution b1 was 461.2 nm.

[0304] <Phosphorus-containing ethylene glycol solution b1'>

[0305] Except for changing the heat treatment conditions to 80°C for 60 minutes, the phosphorus-containing ethylene glycol solution b1' was prepared using the same method as the phosphorus-containing ethylene glycol solution b1. The maximum absorption wavelength of the phosphorus-containing ethylene glycol solution b1' is 470.8 nm.

[0306] Phosphorus-containing ethylene glycol solution b1' was used in Comparative Example 6. Phosphorus-containing ethylene glycol solution b1 was used in all examples and in comparative examples other than Comparative Example 6.

[0307] (3) Manufacturing of polyester resin (A)

[0308] [Example of intermittent polymerization method]

[0309] (Example 1)

[0310] In a 10L stainless steel autoclave equipped with a stirrer, a pre-mixed polyester oligomer with an esterification rate of approximately 95% (composed of high-purity terephthalic acid and ethylene glycol) and high-purity terephthalic acid were added. The esterification reaction was carried out at 260°C to obtain an oligomer mixture. The concentration of acid-terminated groups in the resulting oligomer mixture was 750 eq / ton, and the proportion of hydroxyl-terminated groups (OH%) was 59 mol%.

[0311] A liquefied mixture containing an aluminum-containing ethylene glycol solution a1 and a phosphorus-containing ethylene glycol solution b1 prepared by the above method was added to the resulting oligomer mixture. This mixture was prepared with aluminum and phosphorus elements at 10 ppm and 20 ppm by mass, respectively, relative to the oligomer mixture. It should be noted that the amount of polyester resin (A) generated can be calculated from the amount of terephthalic acid added. In this embodiment, the mixture was added with aluminum and phosphorus elements at 10 ppm and 20 ppm by mass, respectively, relative to the generated polyester resin.

[0312] Then, the system temperature was raised to 280°C within 1 hour, during which the system pressure was slowly reduced to 0.15 kPa. Polycondensation reaction was carried out under these conditions to obtain polyester resin (A) with an IV of 0.60 dl / g.

[0313] (Examples 2-5, Comparative Examples 1-5)

[0314] Except that aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1 were added in the same manner as in Example 1, the polyester resin (A) was obtained.

[0315] (Comparative Example 6)

[0316] Except that the solution b1' was used instead of the solution b1 as a phosphorus-containing ethylene glycol solution, polyester resin (A) was obtained in the same manner as in Example 2.

[0317] The physical properties of the polyester resins (A) obtained in Examples 1-5 and Comparative Examples 1-6 are shown in Table 1. In Table 1 and Table 2 described below, the amount of aluminum added / residual is denoted as Al, the amount of phosphorus added / residual is denoted as P, and the molar ratio of phosphorus to aluminum added / residual is denoted as P / Al.

[0318]

[0319] In the polyester resins (A) of Examples 1-5, although the amounts of aluminum and phosphorus added are small, the polymerization time is shorter, and the back pressure rise coefficient is small due to the small amount of aluminum-based foreign matter, resulting in high quality. In addition, the catalyst addition amount is also small, which reduces the cost of the catalyst.

[0320] Comparative Examples 1 and 2 show that the catalyst cost is high due to the large amount of phosphorus compound added, and the high molar ratio of phosphorus to aluminum is preferred in suppressing aluminum foreign matter, but the polymerization activity is low.

[0321] In Comparative Example 3, although the residual molar ratio of phosphorus to aluminum was within the range of the present invention, the polymerization activity was insufficient and the polymerization time was prolonged due to the insufficient amount of aluminum added.

[0322] Comparative Examples 4 and 5 show that due to the low residual molar ratio of phosphorus to aluminum, the amount of aluminum-based foreign matter in polyester resin (A) increases, the back pressure rise coefficient becomes larger, and the quality of polyester resin (A) is poor.

[0323] In Comparative Example 6, the molar ratio of phosphorus to aluminum was within the range of this invention, resulting in a shorter polymerization time and lower catalyst cost. However, because the maximum absorption wavelength of the phosphorus-containing ethylene glycol solution b1' was significantly larger than in Examples 1-5, the residual molar ratio of phosphorus to aluminum became lower. Furthermore, the increased amount of aluminum-based foreign matter in the polyester resin (A) led to a larger back pressure rise coefficient, thus deteriorating the quality of the polyester resin (A).

[0324] [Example of continuous aggregation method]

[0325] (Example 6)

[0326] In a continuous polyester resin manufacturing apparatus consisting of three continuous esterification reactors and three continuous polycondensation reactors, and equipped with a high-speed agitator in the feed line from the third esterification reactor to the first polycondensation reactor, a slurry prepared by mixing 0.75 parts by mass of ethylene glycol with 1 part by mass of high-purity terephthalic acid is continuously supplied. The reaction is carried out at a temperature of 255°C and a pressure of 203 kPa in the first esterification reactor, a temperature of 261°C and a pressure of 102 kPa in the second esterification reactor, and a temperature of 261-263°C and a pressure of 126 kPa in the third esterification reactor, yielding oligomers. The concentration of acid-terminated groups in the oligomers exiting the third esterification reactor is 550 eq / ton, and the proportion of hydroxyl-terminated groups (OH%) is 60 mol%.

[0327] To the obtained oligomer, a liquefied mixture of aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1, prepared as described above, is added to the conveying line from the third esterification tank to the first polycondensation reactor using a liquid continuous mixer. Specifically, as a catalyst, the aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1, prepared as described above, are mixed relative to the obtained oligomer at 13 ppm by mass of aluminum and 36 ppm by mass of phosphorus, respectively, and added as a liquefied solution. It should be noted that the amount of polyester resin (A) generated can be calculated based on the amount of terephthalic acid added. In this embodiment, the mixture is added at 13 ppm by mass of aluminum and 36 ppm by mass of phosphorus relative to the generated polyester resin (A).

[0328] The oligomer containing the mixture was continuously fed into a continuous polycondensation unit consisting of three reactors. Polycondensation was carried out at a reaction temperature of 268°C and a pressure of 5.3 kPa in the first polycondensation reactor, a reaction temperature of 270°C and a pressure of 0.930 kPa in the second polycondensation reactor, and a reaction temperature of 274°C and a pressure of 0.162 kPa in the third polycondensation reactor, to obtain polyester resin (A) with an IV of 0.59 dl / g. Polyester resin (A) was extruded in strands, cooled in water, cut, and granulated.

[0329] (Examples 7 and 8, Comparative Examples 7 and 8)

[0330] Except that aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1 were added relative to the resulting oligomer in the amounts of catalyst elements shown in Table 2, polyester resin (A) was obtained in the same manner as in Example 6.

[0331] The physical properties of the polyester resins (A) obtained in Examples 6-8 and Comparative Examples 7 and 8 are shown in Table 2.

[0332] Table 2

[0333]

[0334] The production ratio shown in Table 2 refers to the production of Examples 6-8 and Comparative Example 8 per hour, based on the production of Comparative Example 7 per hour (with the production of Comparative Example 7 per hour being 1.00). A production ratio higher than 1 indicates high polymerization activity of the catalyst, while a production ratio lower than 1 indicates low polymerization activity of the catalyst.

[0335] The polyester resins (A) of Examples 6-8 had a higher production yield than those of Comparative Examples 7 and 8, and their polymerization activity was improved even with low amounts of aluminum and phosphorus. Furthermore, due to the low amount of aluminum-based foreign matter in the polyester resin (A), the back pressure rise coefficient was also small, resulting in high-quality polyester resin (A).

[0336] In Comparative Example 8, due to the low residual molar ratio of phosphorus to aluminum, the amount of aluminum-based foreign matter in polyester resin (A) increases, the back pressure rise coefficient increases, and the quality of polyester resin (A) deteriorates.

[0337] Using the results of Examples 1-5 and Comparative Examples 1, 2, 4, and 5 in Table 1, the relationship between the residual molar ratio of phosphorus to aluminum, the amount of aluminum-based foreign matter, and the polymerization time was analyzed. Figure 1 The text indicates that the maximum absorption wavelength of the mixture of aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1 was related to the amount of aluminum-based foreign matter and the polymerization time. Figure 2 The text indicates that the maximum absorption wavelength of the mixture of aluminum-containing ethylene glycol solution a1 and phosphorus-containing ethylene glycol solution b1 is related to the back pressure rise coefficient k. Figure 3 The Chinese side indicated that...

[0338] The values ​​for Comparative Example 3 have been removed from these figures. The reason for this is that although the residual molar ratio of phosphorus to aluminum in Comparative Example 3 was within the range of the present invention, the amount of residual aluminum was too small, which did not allow the catalyst to fully exert its activity, resulting in insufficient polymerization activity compared to other cases.

[0339] Based on these figures, it is clear that the scope of the present invention has a critical significance. Furthermore, it is clear that the amount of aluminum-based foreign matter and the polymerization time are mutually exclusive. It should be noted that, since the polyester resin (A) obtained in Examples 1 and 6 are also used below, the polyester resin (A) obtained in Example 1 is referred to as polyester resin (A-1), and the polyester resin (A) obtained in Example 6 is referred to as polyester resin (A-2).

[0340] (4) Manufacturing of masterbatch containing anti-blocking agent (B)

[0341] [Example of the polymerization process addition method]

[0342] (Manufacturing Example 1-1)

[0343] (i) Preparation of ethylene glycol slurry containing silica

[0344] Add 5L of ethylene glycol and 600g of silica particles (Sylysia 310) with a volume average particle size of 2.4μm as an anti-blocking agent to a dispersion tank equipped with a homogenizer. Disperse and stir at 8000rpm for 2 hours to prepare a slurry with a volume of 120g / L.

[0345] (ii) Method for manufacturing masterbatch (B-1) containing silica

[0346] In a stainless steel autoclave equipped with a stirrer, distillation column, and pressure regulator, 1297 parts by mass of high-purity terephthalic acid, 678 parts by mass of ethylene glycol, and an ethylene glycol slurry containing silica particles prepared by the above method were added to achieve a SiO2 particle content of 0.7% by mass relative to the mass of the obtained polyester resin. Further, 6 parts by mass of triethylamine and 0.05 parts by mass of sodium acetate were added, and an esterification reaction was carried out using a conventional method to obtain an oligomer mixture. In this oligomer mixture, an aluminum-containing ethylene glycol solution a1 and a phosphorus-containing ethylene glycol solution b1 prepared by the above method were added at 40 ppm and 95 ppm respectively, relative to the mass of the obtained polyester resin, calculated as aluminum and phosphorus.

[0347] Subsequently, the system temperature was raised to 280℃ within 1 hour, while the system pressure was gradually reduced to 0.15 kPa. Under these conditions, a polycondensation reaction was carried out to obtain a silica-containing masterbatch (B-1) with an IV of 0.59 dl / g. The obtained silica-containing masterbatch (B-1) had 68 coarse particles, indicating a low number of coarse particles and high quality.

[0348] [Example of melt mixing method]

[0349] (Manufacturing Examples 1-2)

[0350] Polyester resin (A-2) and silica particles (Sylysia 310, manufactured by Fuji Silicon Chemicals) with a volume average particle size of 2.4 μm, used as an anti-blocking agent, were mixed in a ratio of 90 parts by weight and 10 parts by weight, respectively. The mixture was then melt-blended using a twin-screw extruder (TEX30α, manufactured by Nippon Steel Works) at a barrel temperature of 300°C to obtain silica-containing masterbatch (B-2). The obtained silica-containing masterbatch (B-2) had 120 coarse particles, indicating a low number of coarse particles and high quality.

[0351] (5) Manufacturing of single-layer polyester film (part 1)

[0352] (Example 9)

[0353] A polyester resin composition, consisting of polyester resin (A-1) and silica-containing masterbatch (B-2) mixed at a mass ratio of 98.8:1.2, was vacuum dried at 135°C for 10 hours. The mixture was then metered and fed into a twin-screw extruder, extruded into sheets at 280°C, and quenched on a metal roller with a surface temperature maintained at 20°C to obtain a cast film with a thickness of 1400 μm. During quenching on the metal roller, adhesion to the roller was enhanced using an electrostatic adhesion device composed of saw-shaped electrodes.

[0354] The cast film was then heated to 100°C using heated rollers and an infrared heater, and subsequently stretched 3.5 times in length using rollers with a differential circumferential speed to obtain a uniaxially oriented film. Next, it was stretched 4.0 times in width at 120°C using a tenter frame. With the film width fixed, it was heated at 260°C for 0.5 seconds using an infrared heater, and further relaxed at 200°C for 23 seconds with a 3% relaxation rate to obtain a biaxially oriented polyester film with a thickness of 100 μm.

[0355] The resulting polyester film has a static friction coefficient (μs) of 0.50 and good slip properties, making it a film with excellent operational characteristics such as running stability, wear resistance, and winding properties.

[0356] (Example 10)

[0357] Except that polyester resin (A-2) was used instead of polyester resin (A-1), the biaxially oriented polyester film was prepared using the same method as in Example 9. The resulting polyester film had a static friction coefficient (μs) of 0.50 and good slip properties, making it a film with excellent operational characteristics such as running stability, wear resistance, and winding properties.

[0358] (Comparative Example 9)

[0359] Except for not mixing with silica-containing masterbatch (B-2) and only vacuum drying polyester resin (A-1), a biaxially oriented polyester film was prepared using the same method as in Example 9. The resulting polyester film had a static friction coefficient (μs) of 1 or higher, and could be considered a film with poor slip properties and poor operational characteristics such as running stability, wear resistance, and winding properties.

[0360] (Comparative Example 10)

[0361] Except for not mixing with silica-containing masterbatch (B-2) and only vacuum drying polyester resin (A-2), a biaxially oriented polyester film was prepared using the same method as in Example 10. The resulting polyester film had a static friction coefficient (μs) of 1 or higher, and can be considered a film with poor slip properties and poor operational characteristics such as running stability, wear resistance, and winding properties.

[0362] (6) Manufacturing of masterbatch (C) containing electrostatic adhesion promoter

[0363] (Manufacturing Examples 2-1 to 5)

[0364] High-purity terephthalic acid, ethylene glycol, and triethylamine were added to a stainless steel autoclave equipped with a stirrer, distillation column, and pressure regulator. An esterification reaction was carried out using conventional methods to obtain an oligomer mixture. Basic aluminum acetate, magnesium acetate dihydrate, potassium acetate, and triethyl phosphate were added to this oligomer mixture in the amounts of aluminum, magnesium, potassium, and phosphorus shown in Table 3, respectively.

[0365] Then, the system temperature was raised to 280°C within 1 hour, and the system pressure was slowly reduced to 0.15 kPa during this period. Under these conditions, a polycondensation reaction was carried out for 80 minutes to obtain masterbatch (C) containing electrostatic adhesion promoter.

[0366] The physical properties of the masterbatch (C) containing the electrostatic adhesion promoter are shown in Table 3. It should be noted that, hereafter, the masterbatch (C) containing the electrostatic adhesion promoter manufactured in Manufacturing Example 2-1 will be referred to as the masterbatch (C-1) containing the electrostatic adhesion promoter, and the masterbatch (C) containing the electrostatic adhesion promoter manufactured in Manufacturing Example 2-2 will be referred to as the masterbatch (C-2) containing the electrostatic adhesion promoter.

[0367] Table 3

[0368]

[0369] By adjusting the content of magnesium, alkali metal, and phosphorus in the masterbatch (C) to the preferred range described above, the masterbatches (C-1) and (C-2) containing the electrostatic adhesion promoter can suppress coloring (Co-b) and improve electrostatic adhesion (by reducing the melt resistivity ρi).

[0370] (7) Manufacturing of single-layer polyester film (part 2)

[0371] (Example 11)

[0372] Polyester resin (A-2), silica-containing masterbatch (B-1), and masterbatch containing an electrostatic adhesion promoter (C-1) were mixed in the proportions shown in Table 4 and vacuum-dried at 135°C for 10 hours. Subsequently, the mixture was metered and fed into a twin-screw extruder and extruded in sheet form at 280°C. The extruded film was then rapidly cured on metal rollers with a surface temperature maintained at 20°C to obtain a cast film with a thickness of 1680 μm.

[0373] The cast film was then heated to 100°C using heated rollers and an infrared heater, and subsequently stretched 3.5 times its original length using rollers with a differential circumferential speed to obtain a uniaxially oriented film. Next, it was stretched 4.0 times its original width using a tenter frame at 120°C. With the film width fixed, it was heated at 260°C for 0.5 seconds using an infrared heater, and further relaxed at 200°C for 23 seconds with a 3% relaxation rate to obtain a biaxially oriented polyester film with a thickness of 12 μm.

[0374] (Example 12)

[0375] Except that a silica-containing masterbatch (B-2) is used instead of a silica-containing masterbatch (B-1), and the mixing ratio is changed to the proportions shown in Table 4, the biaxially oriented polyester film is produced in the same manner as in Example 11.

[0376] (Comparative Example 11)

[0377] Except for not mixing with silica-containing masterbatch (B-1) and using only polyester resin (A-2), the biaxially oriented polyester film was produced using the same method as in Example 11.

[0378] The physical properties of the polyester films obtained in Examples 11-12 and Comparative Example 11 are shown in Table 4.

[0379] Table 4

[0380]

[0381] The polyester films of Examples 11 and 12 exhibit excellent electrostatic adhesion, enabling faster film fabrication. The resulting polyester films of Examples 11 and 12 also possess excellent slip properties.

[0382] On the other hand, the polyester film obtained by Comparative Example 11 had poor electrostatic adhesion and slip properties, resulting in low quality.

[0383] (8) Manufacturing of composite masterbatch (D)

[0384] (Manufacturing Example 3)

[0385] In the polymerization method of the masterbatch (C) containing the electrostatic adhesion promoter described in (6) above, in addition to adding high-purity terephthalic acid, ethylene glycol, and triethylamine, as well as the ethylene glycol slurry of silica particles prepared by the method described in (4) above at a SiO2 particle content of 0.7% by mass relative to the mass of the obtained polyester resin, an IV of 0.50 dl / g and a melt resistivity ρi of 0.10 × 10⁻⁶ were obtained by the same method as in Manufacturing Example 2-1. 8 Composite masterbatch (D-1) with Ω·cm and Co-b of 15.8.

[0386] The resulting composite masterbatch (D-1) had 81 coarse particles, which is of the same high quality as manufacturing example 2-1.

[0387] (9) Manufacturing of a three-layer polyester film

[0388] (Example 13)

[0389] In Example 11, the melt extrusion method was changed to a 3-layer method with 3 extruders, and the thickness ratio of the surface layer / intermediate layer / surface layer was 0.11 / 0.78 / 0.11. The polyester resin composition of the surface layer was the same as in Example 11, except that the polyester resin composition of the intermediate layer was set to polyester resin (A-2) / masterbatch containing electrostatic adhesion promoter (C-1) = 95 / 5 (mass ratio). The biaxially oriented polyester film with a total thickness of 12 μm was produced by the same method as in Example 11.

[0390] The resulting polyester film has the same productivity and slip properties as the polyester film obtained in Example 11, and exhibits excellent transparency as assessed by visual inspection.

[0391] (Example 14)

[0392] Except that the surface polyester resin composition was set to polyester resin (A-2) / composite masterbatch (D-1) = 95 / 5 (mass ratio), a twin-screw stretched polyester film with a total thickness of 12 μm was obtained by the same method as in Example 13.

[0393] The resulting polyester film has the same productivity and slip properties as the polyester film obtained in Example 11, and exhibits excellent transparency as assessed by visual inspection.

[0394] The physical properties of the polyester films obtained in Examples 13-14 are shown in Table 5.

[0395]

[0396] [Availability in Industry]

[0397] The polyester resin composition obtained by the manufacturing method of the present invention reduces the catalyst cost problem of the polyester resin composition obtained by polymerization using aluminum and phosphorus compounds, while improving the productivity of the polyester resin composition and reducing foreign matter from the catalyst contained in the polyester resin composition. Therefore, a clean, high-quality polyester resin composition can be provided.

[0398] Furthermore, the polyester film manufactured using the above-described polyester resin composition has a smooth texture. Additionally, by forming the film using the above-described polyester resin composition with the addition of an electrostatic adhesion promoter, the melt resistivity can be sufficiently reduced. Moreover, when using the above-described polyester resin composition containing a masterbatch with low impurities, excellent color tone, and superior thermal stability, a polyester film of excellent quality can be manufactured while improving film-forming properties.

[0399] Therefore, polyester films manufactured using the polyester resin composition of the present invention can be used in a wide range of applications, such as antistatic films, easy-to-adhere films, cards, sealed containers, agricultural applications, building materials, decorative materials, wallpaper, OHP films, printing, inkjet printing, sublimation transfer recording, laser printer recording, electronic photo printing, thermal transfer recording, thermal transfer recording, printed circuit board wiring, membrane switches, near-infrared absorption films for plasma displays, transparent conductive films for touch panels and electroluminescence, masking films, photolithography, X-ray films, photographic film films, phase retardation films, polarizing films, polarizing film protection (TAC), deflection plates, protective films for phase retardation plate inspection and / or diaphragms, photosensitive resin films, field-of-view magnification films, diffusers, reflective films, anti-reflective films, UV protection films, and back-abrasion tapes.

Claims

1. A method for manufacturing a polyester resin composition, characterized in that, The process includes a mixed matrix polyester resin (A) and a masterbatch (B) containing an anti-blocking agent, wherein the matrix polyester resin (A) contains an aluminum compound and a phosphorus compound and satisfies the following (1) to (4). (1) The aluminum content in the matrix polyester resin (A) is 9~19 ppm by mass. (2) The phosphorus content in the matrix polyester resin (A) is 13~31 ppm by mass. (3) The molar ratio of phosphorus to aluminum in the matrix polyester resin (A) is between 1.32 and 1.

80. (4) The matrix polyester resin (A) contains substances derived from the polymerization catalyst, which contains only polymerization catalysts composed of aluminum compounds and phosphorus compounds.

2. The method for manufacturing the polyester resin composition according to claim 1, wherein, The masterbatch (B) contains insoluble particles that are insoluble in the matrix polyester resin (A), the volume average particle size of which is 0.5 to 3.0 μm, and the content of the insoluble particles is 0.5 to 20% by mass.

3. The method for manufacturing the polyester resin composition according to claim 1 or 2, wherein, Further mix the masterbatch (C) containing the electrostatic adhesion promoter.

4. The method for manufacturing the polyester resin composition according to claim 3, wherein, The masterbatch (C) is a polyester resin containing magnesium compounds, alkali metal compounds and phosphorus compounds. The masterbatch (C) contains 400~2700 ppm by mass of magnesium, 40~270 ppm by mass of alkali metals and 200~1700 ppm by mass of phosphorus.

5. The method for manufacturing the polyester resin composition according to claim 1 or 2, wherein, Instead of the masterbatch (B), a masterbatch (D) containing an anti-blocking agent and an electrostatic adhesion promoter is mixed with the base polyester resin (A).

6. The method for manufacturing the polyester resin composition according to claim 5, wherein, The masterbatch (D) contains insoluble particles that are insoluble in the matrix polyester resin (A), the volume average particle size of the insoluble particles being 0.5 to 3.0 μm, and the content of the insoluble particles being 0.5 to 20% by mass. Further, the masterbatch (D) is a polyester resin containing magnesium compounds, alkali metal compounds, and phosphorus compounds, and the masterbatch (D) contains 400 to 2700 ppm by mass of magnesium, 40 to 270 ppm by mass of alkali metals, and 200 to 1700 ppm by mass of phosphorus.

7. The method for manufacturing the polyester resin composition according to claim 4, wherein, The alkali metal in the alkali metal compound contained in the masterbatch (C) is potassium.

8. The method for manufacturing the polyester resin composition according to claim 4, wherein, The phosphorus compound contained in the masterbatch (C) is a trialkyl phosphate, wherein at least one of the alkyl groups of the trialkyl phosphate is an alkyl group having 2 to 4 carbon atoms.

9. The method for manufacturing the polyester resin composition according to claim 6, wherein, The alkali metal in the alkali metal compound contained in the masterbatch (D) is potassium.

10. The method for manufacturing the polyester resin composition according to claim 6, wherein, The phosphorus compound contained in the masterbatch (D) is a trialkyl phosphate, wherein at least one of the alkyl groups of the trialkyl phosphate is an alkyl group having 2 to 4 carbon atoms.

11. The method for manufacturing the polyester resin composition according to claim 8, wherein, The phosphorus compound contained in the masterbatch (C) is triethyl phosphate.

12. The method for manufacturing the polyester resin composition according to claim 10, wherein, The phosphorus compound contained in the masterbatch (D) is triethyl phosphate.

13. The method for manufacturing the polyester resin composition according to claim 3, wherein, The melt resistivity of the masterbatch (C) is 0.005 × 10⁻⁶. 8 ~0.05×10 8 Ω・cm.

14. The method for manufacturing the polyester resin composition according to claim 3, wherein, The masterbatch (C) is a polyester with dicarboxylic acid and diol as its constituent components. When the amount of magnesium relative to the dicarboxylic acid is set as m, the amount of alkali metal is set as k, and the amount of phosphorus is set as p, the following (4) is satisfied, where the units of m, k, and p are mol%. (4) 2≤(m+k / 2) / p≤3.

5.

15. The method for manufacturing the polyester resin composition according to claim 5, wherein, The melt resistivity of the masterbatch (D) is 0.005 × 10⁻⁶. 8 ~0.05×10 8 Ω・cm.

16. The method for manufacturing the polyester resin composition according to claim 5, wherein, The masterbatch (D) is a polyester composed of dicarboxylic acid and diol components. When the amount of magnesium relative to the dicarboxylic acid component is set as m, the amount of alkali metal is set as k, and the amount of phosphorus is set as p, the following (4) is satisfied, where the units of m, k, and p are mol%. (4) 2≤(m+k / 2) / p≤3.

5.

17. The method for manufacturing the polyester resin composition according to claim 1 or 2, wherein, The phosphorus compound contained in the matrix polyester resin (A) has a phosphorus element and a phenol structure within the same molecule.

18. The method for manufacturing the polyester resin composition according to claim 1 or 2, wherein, The aluminum content in the matrix polyester resin (A), which is equivalent to aluminum-based foreign matter, is less than 3000 ppm by mass.

19. The method for manufacturing the polyester resin composition according to claim 1 or 2, wherein, The intrinsic viscosity (IV) of the matrix polyester resin (A) is 0.56 dl / g or higher.

20. The method for manufacturing the polyester resin composition according to claim 1 or 2, wherein the method for manufacturing the matrix polyester resin (A) comprises a first step of synthesizing a polyester or an oligomer thereof as an intermediate condensation polymer, and a second step of further condensing the intermediate. After step 1 and before step 2, a solution A1 containing dissolved aluminum compound and a solution B1 containing dissolved phosphorus compound are added to the intermediate, wherein the amounts of solution A1 and solution B1 added satisfy the following (5) to (7). (5) The amount of aluminum added relative to the generated matrix polyester resin (A) is 9~19 ppm by mass. (6) The amount of phosphorus added relative to the generated matrix polyester resin (A) is 18~38 ppm by mass. (7) The molar ratio of the amount of phosphorus added in (6) to the amount of aluminum added in (5) is more than 1.50 and less than 2.

30.

21. The method for manufacturing the polyester resin composition according to claim 20, wherein, The matrix polyester resin (A) is manufactured by a batch polymerization method.

22. The method for manufacturing the polyester resin composition according to claim 20, wherein, The matrix polyester resin (A) is manufactured by continuous polymerization, and the solution A1 and the solution B1 are added to the final esterification reactor or the delivery line between the final esterification reactor and the initial polymerization reactor.

23. The method for manufacturing the polyester resin composition according to claim 20, wherein, The solution A1 is a diol solution, and the maximum absorption wavelength of the solution A1 is 562.0~572.0 nm.

24. The method for manufacturing the polyester resin composition according to claim 23, wherein, Solution B1 is a diol solution, and the maximum absorption wavelength of solution B1 is 458.0~465.0 nm.

25. The method for manufacturing the polyester resin composition according to claim 20, wherein, The solutions A1 and B1 are diol solutions, and the maximum absorption wavelength of the mixture of diol solution A1 and diol solution B1 is 559.5~560.8 nm.

Citation Information

Patent Citations

  • Polyester and method for producing polyester

    JP2006169432A

  • Building and entrance storage

    JP2020153075A

  • Polyester, process for production of polyester, and polyester molded article

    WO2007032325A1

  • Polyester composition and polyester film

    WO2013146524A1

  • Polyester composition and polyester film

    CN104204089A